Optogenetic inhibition-mediated activity-dependent modification of CA1 pyramidal-interneuron connections during behavior - Gridchyn, Igor; Schönenberger, Philipp; O'Neill, Joseph; Csicsvari, Jozsef L (eLife)
In vitro work revealed that excitatory synaptic inputs to hippocampal inhibitory interneurons could undergo Hebbian, associative, or non-associative plasticity. Both behavioral and learning-dependent reorganization of these connections has also been demonstrated by measuring spike transmission probabilities in pyramidal cell-interneuron spike cross-correlations that indicate monosynaptic connections. Here we investigated the activity-dependent modification of these connections during exploratory behavior in rats by optogenetically inhibiting pyramidal cell and interneuron subpopulations. Light application and associated firing alteration of pyramidal and interneuron populations led to lasting changes in pyramidal-interneuron connection weights as indicated by spike transmission changes. Spike transmission alterations were predicted by the light-mediated changes in the number of pre- and postsynaptic spike pairing events and by firing rate changes of interneurons but not pyramidal cells. This work demonstrates the presence of activity-dependent associative and non-associative reorganization of pyramidal-interneuron connections triggered by the optogenetic modification of the firing rate and spike synchrony of cells.

Supplementary data for "Computational design of curved thin shells: from glass façades to programmable matter" - Guseinov, Ruslan
Supplementary movies showing the following sequences for spatio-temporarily programmed shells: input geometry and actuation time landscape; comparison of morphing processes from a camera recording and a simulation; final actuated shape.

Supplementary data for "Zero field splitting of heavy-hole states in quantum dots" - Katsaros, Georgios
These are the supplementary research data to the publication "Zero field splitting of heavy-hole states in quantum dots". All matrix files have the same format. Within each column the bias voltage is changed. Each column corresponds to either a different gate voltage or magnetic field. The voltage values are given in mV, the current values in pA. Find a specific description in the included Readme file.

Supplementary data for "Computational design of cold bent glass façades" - Guseinov, Ruslan

Optogenetic alteration of hippocampal network activity - Csicsvari, Jozsef L; Gridchyn, Igor; Schönenberger, Philipp
Supplementary data provided for the provided for the publication: Igor Gridchyn , Philipp Schoenenberger , Joseph O'Neill , Jozsef Csicsvari (2020) Optogenetic inhibition-mediated activity-dependent modification of CA1 pyramidal-interneuron connections during behavior. Elife.

Programming temporal morphing of self-actuated shells - Guseinov, Ruslan; McMahan, Connor; Perez Rodriguez, Jesus; Daraio, Chiara; Bickel, Bernd (Nature Communications)
Advances in shape-morphing materials, such as hydrogels, shape-memory polymers and light-responsive polymers have enabled prescribing self-directed deformations of initially flat geometries. However, most proposed solutions evolve towards a target geometry without considering time-dependent actuation paths. To achieve more complex geometries and avoid self-collisions, it is critical to encode a spatial and temporal shape evolution within the initially flat shell. Recent realizations of time-dependent morphing are limited to the actuation of few, discrete hinges and cannot form doubly curved surfaces. Here, we demonstrate a method for encoding temporal shape evolution in architected shells that assume complex shapes and doubly curved geometries. The shells are non-periodic tessellations of pre-stressed contractile unit cells that soften in water at rates prescribed locally by mesostructure geometry. The ensuing midplane contraction is coupled to the formation of encoded curvatures. We propose an inverse design tool based on a data-driven model for unit cells’ temporal responses.
Keywords: Design; Synthesis and processing; Mechanical engineering; Polymers

STL-files for 3D-printed grid holders described in Fäßler F, Zens B, et al.; 3D printed cell culture grid holders for improved cellular specimen preparation in cryo-electron microscopy - Schur, Florian KM
Cryo-electron microscopy (cryo-EM) of cellular specimens provides insights into biological processes and structures within a native context. However, a major challenge still lies in the efficient and reproducible preparation of adherent cells for subsequent cryo-EM analysis. This is due to the sensitivity of many cellular specimens to the varying seeding and culturing conditions required for EM experiments, the often limited amount of cellular material and also the fragility of EM grids and their substrate. Here, we present low-cost and reusable 3D printed grid holders, designed to improve specimen preparation when culturing challenging cellular samples directly on grids. The described grid holders increase cell culture reproducibility and throughput, and reduce the resources required for cell culturing. We show that grid holders can be integrated into various cryo-EM workflows, including micro-patterning approaches to control cell seeding on grids, and for generating samples for cryo-focused ion beam milling and cryo-electron tomography experiments. Their adaptable design allows for the generation of specialized grid holders customized to a large variety of applications.

A persistent homology perspective to the link prediction problem - Bhatia, Sumit; Chatterjee, Bapi; Nathani, Deepak; Kaul, Manohar (Complex Networks and their applications VIII)
Persistent homology is a powerful tool in Topological Data Analysis (TDA) to capture the topological properties of data succinctly at different spatial resolutions. For graphical data, the shape, and structure of the neighborhood of individual data items (nodes) are an essential means of characterizing their properties. We propose the use of persistent homology methods to capture structural and topological properties of graphs and use it to address the problem of link prediction. We achieve encouraging results on nine different real-world datasets that attest to the potential of persistent homology-based methods for network analysis.

Asynchronous distributed key generation for computationally-secure randomness, consensus, and threshold signatures - Kokoris Kogias, Eleftherios; Malkhi, Dahlia; Spiegelman, Alexander (Proceedings of the 2020 ACM SIGSAC Conference on Computer and Communications Security)
In this paper, we present the first Asynchronous Distributed Key Generation (ADKG) algorithm which is also the first distributed key generation algorithm that can generate cryptographic keys with a dual (f,2f+1)-threshold (where f is the number of faulty parties). As a result, using our ADKG we remove the trusted setup assumption that the most scalable consensus algorithms make. In order to create a DKG with a dual (f,2f+1)- threshold we first answer in the affirmative the open question posed by Cachin et al. [7] on how to create an Asynchronous Verifiable Secret Sharing (AVSS) protocol with a reconstruction threshold of f+1<k łe 2f+1, which is of independent interest. Our High-threshold-AVSS (HAVSS) uses an asymmetric bivariate polynomial to encode the secret. This enables the reconstruction of the secret only if a set of k nodes contribute while allowing an honest node that did not participate in the sharing phase to recover his share with the help of f+1 honest parties. Once we have HAVSS we can use it to bootstrap scalable partially synchronous consensus protocols, but the question on how to get a DKG in asynchrony remains as we need a way to produce common randomness. The solution comes from a novel Eventually Perfect Common Coin (EPCC) abstraction that enables the generation of a common coin from n concurrent HAVSS invocations. EPCC's key property is that it is eventually reliable, as it might fail to agree at most f times (even if invoked a polynomial number of times). Using EPCC we implement an Eventually Efficient Asynchronous Binary Agreement (EEABA) which is optimal when the EPCC agrees and protects safety when EPCC fails. Finally, using EEABA we construct the first ADKG which has the same overhead and expected runtime as the best partially-synchronous DKG (O(n4) words, O(f) rounds). As a corollary of our ADKG, we can also create the first Validated Asynchronous Byzantine Agreement (VABA) that does not need a trusted dealer to setup threshold signatures of degree n-f. Our VABA has an overhead of expected O(n2) words and O(1) time per instance, after an initial O(n4) words and O(f) time bootstrap via ADKG.

Hybridization for stability verification of nonlinear switched systems - Garcia Soto, Miriam; Prabhakar, Pavithra (2020 IEEE Real-Time Systems Symposium)
We propose a novel hybridization method for stability analysis that over-approximates nonlinear dynamical systems by switched systems with linear inclusion dynamics. We observe that existing hybridization techniques for safety analysis that over-approximate nonlinear dynamical systems by switched affine inclusion dynamics and provide fixed approximation error, do not suffice for stability analysis. Hence, we propose a hybridization method that provides a state-dependent error which converges to zero as the state tends to the equilibrium point. The crux of our hybridization computation is an elegant recursive algorithm that uses partial derivatives of a given function to obtain upper and lower bound matrices for the over-approximating linear inclusion. We illustrate our method on some examples to demonstrate the application of the theory for stability analysis. In particular, our method is able to establish stability of a nonlinear system which does not admit a polynomial Lyapunov function.

Optimal rate for Bose-Einstein condensation in the Gross-Pitaevskii regime - Boccato, Chiara; Brennecke, Christian; Cenatiempo, Serena; Schlein, Benjamin (Communications in Mathematical Physics)
We consider systems of bosons trapped in a box, in the Gross–Pitaevskii regime. We show that low-energy states exhibit complete Bose–Einstein condensation with an optimal bound on the number of orthogonal excitations. This extends recent results obtained in Boccato et al. (Commun Math Phys 359(3):975–1026, 2018), removing the assumption of small interaction potential.

Mechanisms of zebrafish epiboly: A current view - Bruce, Ashley E.E.; Heisenberg, Carl-Philipp J (Gastrulation: From Embryonic Pattern to Form)
Epiboly is a conserved gastrulation movement describing the thinning and spreading of a sheet or multi-layer of cells. The zebrafish embryo has emerged as a vital model system to address the cellular and molecular mechanisms that drive epiboly. In the zebrafish embryo, the blastoderm, consisting of a simple squamous epithelium (the enveloping layer) and an underlying mass of deep cells, as well as a yolk nuclear syncytium (the yolk syncytial layer) undergo epiboly to internalize the yolk cell during gastrulation. The major events during zebrafish epiboly are: expansion of the enveloping layer and the internal yolk syncytial layer, reduction and removal of the yolk membrane ahead of the advancing blastoderm margin and deep cell rearrangements between the enveloping layer and yolk syncytial layer to thin the blastoderm. Here, work addressing the cellular and molecular mechanisms as well as the sources of the mechanical forces that underlie these events is reviewed. The contribution of recent findings to the current model of epiboly as well as open questions and future prospects are also discussed.

KS(conf): A light-weight test if a multiclass classifier operates outside of its specifications - Sun, Rémy; Lampert, Christoph (International Journal of Computer Vision)
We study the problem of automatically detecting if a given multi-class classifier operates outside of its specifications (out-of-specs), i.e. on input data from a different distribution than what it was trained for. This is an important problem to solve on the road towards creating reliable computer vision systems for real-world applications, because the quality of a classifier’s predictions cannot be guaranteed if it operates out-of-specs. Previously proposed methods for out-of-specs detection make decisions on the level of single inputs. This, however, is insufficient to achieve low false positive rate and high false negative rates at the same time. In this work, we describe a new procedure named KS(conf), based on statistical reasoning. Its main component is a classical Kolmogorov–Smirnov test that is applied to the set of predicted confidence values for batches of samples. Working with batches instead of single samples allows increasing the true positive rate without negatively affecting the false positive rate, thereby overcoming a crucial limitation of single sample tests. We show by extensive experiments using a variety of convolutional network architectures and datasets that KS(conf) reliably detects out-of-specs situations even under conditions where other tests fail. It furthermore has a number of properties that make it an excellent candidate for practical deployment: it is easy to implement, adds almost no overhead to the system, works with any classifier that outputs confidence scores, and requires no a priori knowledge about how the data distribution could change.

Proving expected sensitivity of probabilistic programs with randomized variable-dependent termination time - Wang, Peixin; Fu, Hongfei; Chatterjee, Krishnendu; Deng, Yuxin; Xu, Ming (Proceedings of the ACM on Programming Languages)
The notion of program sensitivity (aka Lipschitz continuity) specifies that changes in the program input result in proportional changes to the program output. For probabilistic programs the notion is naturally extended to expected sensitivity. A previous approach develops a relational program logic framework for proving expected sensitivity of probabilistic while loops, where the number of iterations is fixed and bounded. In this work, we consider probabilistic while loops where the number of iterations is not fixed, but randomized and depends on the initial input values. We present a sound approach for proving expected sensitivity of such programs. Our sound approach is martingale-based and can be automated through existing martingale-synthesis algorithms. Furthermore, our approach is compositional for sequential composition of while loops under a mild side condition. We demonstrate the effectiveness of our approach on several classical examples from Gambler's Ruin, stochastic hybrid systems and stochastic gradient descent. We also present experimental results showing that our automated approach can handle various probabilistic programs in the literature.

Anatomical specializations related to foraging in the visual system of a nocturnal insectivorous bird, the band-winged nightjar (Aves: Caprimulgiformes) - Salazar, Juan Esteban; Severin, Daniel; Vega Zuniga, Tomas A; Fernández-Aburto, Pedro; Deichler, Alfonso; Sallaberry A., Michel; Mpodozis, Jorge (Brain, Behavior and Evolution)
Nocturnal animals that rely on their visual system for foraging, mating, and navigation usually exhibit specific traits associated with living in scotopic conditions. Most nocturnal birds have several visual specializations, such as enlarged eyes and an increased orbital convergence. However, the actual role of binocular vision in nocturnal foraging is still debated. Nightjars (Aves: Caprimulgidae) are predators that actively pursue and capture flying insects in crepuscular and nocturnal environments, mainly using a conspicuous “sit-and-wait” tactic on which pursuit begins with an insect flying over the bird that sits on the ground. In this study, we describe the visual system of the band-winged nightjar (Systellura longirostris), with emphasis on anatomical features previously described as relevant for nocturnal birds. Orbit convergence, determined by 3D scanning of the skull, was 73.28°. The visual field, determined by ophthalmoscopic reflex, exhibits an area of maximum binocular overlap of 42°, and it is dorsally oriented. The eyes showed a nocturnal-like normalized corneal aperture/axial length index. Retinal ganglion cells (RGCs) were relatively scant, and distributed in an unusual oblique-band pattern, with higher concentrations in the ventrotemporal quadrant. Together, these results indicate that the band-winged nightjar exhibits a retinal specialization associated with the binocular area of their dorsal visual field, a relevant area for pursuit triggering and prey attacks. The RGC distribution observed is unusual among birds, but similar to that of some visually dependent insectivorous bats, suggesting that those features might be convergent in relation to feeding strategies.

Correlated random matrices: Band rigidity and edge universality - Alt, Johannes; Erdös, László; Krüger, Torben H; Schröder, Dominik J (Annals of Probability)
We prove edge universality for a general class of correlated real symmetric or complex Hermitian Wigner matrices with arbitrary expectation. Our theorem also applies to internal edges of the self-consistent density of states. In particular, we establish a strong form of band rigidity which excludes mismatches between location and label of eigenvalues close to internal edges in these general models.

TOLs function as ubiquitin receptors in the early steps of the ESCRT pathway in higher plants - Moulinier-Anzola, Jeanette; Schwihla, Maximilian; De-Araújo, Lucinda; Artner, Christina; Jörg, Lisa; Konstantinova, Nataliia; Luschnig, Christian; Korbei, Barbara (Molecular Plant)
Protein abundance and localization at the plasma membrane (PM) shapes plant development and mediates adaptation to changing environmental conditions. It is regulated by ubiquitination, a post-translational modification crucial for the proper sorting of endocytosed PM proteins to the vacuole for subsequent degradation. To understand the significance and the variety of roles played by this reversible modification, the function of ubiquitin receptors, which translate the ubiquitin signature into a cellular response, needs to be elucidated. In this study, we show that TOL (TOM1-like) proteins function in plants as multivalent ubiquitin receptors, governing ubiquitinated cargo delivery to the vacuole via the conserved Endosomal Sorting Complex Required for Transport (ESCRT) pathway. TOL2 and TOL6 interact with components of the ESCRT machinery and bind to K63-linked ubiquitin via two tandemly arranged conserved ubiquitin-binding domains. Mutation of these domains results not only in a loss of ubiquitin binding but also altered localization, abolishing TOL6 ubiquitin receptor activity. Function and localization of TOL6 is itself regulated by ubiquitination, whereby TOL6 ubiquitination potentially modulates degradation of PM-localized cargoes, assisting in the fine-tuning of the delicate interplay between protein recycling and downregulation. Taken together, our findings demonstrate the function and regulation of a ubiquitin receptor that mediates vacuolar degradation of PM proteins in higher plants.
Keywords: Plant Science; Molecular Biology

Molecular recognition at septin interfaces: The switches hold the key - Rosa, Higor Vinícius Dias; Leonardo, Diego Antonio; Brognara, Gabriel; Brandão-Neto, José; D'Muniz Pereira, Humberto; Araújo, Ana Paula Ulian; Garratt, Richard Charles (Journal of Molecular Biology)
The assembly of a septin filament requires that homologous monomers must distinguish between one another in establishing appropriate interfaces with their neighbors. To understand this phenomenon at the molecular level, we present the first four crystal structures of heterodimeric septin complexes. We describe in detail the two distinct types of G-interface present within the octameric particles, which must polymerize to form filaments. These are formed between SEPT2 and SEPT6 and between SEPT7 and SEPT3, and their description permits an understanding of the structural basis for the selectivity necessary for correct filament assembly. By replacing SEPT6 by SEPT8 or SEPT11, it is possible to rationalize Kinoshita's postulate, which predicts the exchangeability of septins from within a subgroup. Switches I and II, which in classical small GTPases provide a mechanism for nucleotide-dependent conformational change, have been repurposed in septins to play a fundamental role in molecular recognition. Specifically, it is switch I which holds the key to discriminating between the two different G-interfaces. Moreover, residues which are characteristic for a given subgroup play subtle, but pivotal, roles in guaranteeing that the correct interfaces are formed.
Keywords: Molecular Biology; Structural Biology

A model for soap film dynamics with evolving thickness - Ishida, Sadashige; Synak, Peter; Narita, Fumiya; Hachisuka, Toshiya; Wojtan, Christopher J (ACM Transactions on Graphics)
Previous research on animations of soap bubbles, films, and foams largely focuses on the motion and geometric shape of the bubble surface. These works neglect the evolution of the bubble’s thickness, which is normally responsible for visual phenomena like surface vortices, Newton’s interference patterns, capillary waves, and deformation-dependent rupturing of films in a foam. In this paper, we model these natural phenomena by introducing the film thickness as a reduced degree of freedom in the Navier-Stokes equations and deriving their equations of motion. We discretize the equations on a nonmanifold triangle mesh surface and couple it to an existing bubble solver. In doing so, we also introduce an incompressible fluid solver for 2.5D films and a novel advection algorithm for convecting fields across non-manifold surface junctions. Our simulations enhance state-of-the-art bubble solvers with additional effects caused by convection, rippling, draining, and evaporation of the thin film.

Graph sparsification for derandomizing massively parallel computation with low space - Czumaj, Artur; Davies, Peter; Parter, Merav (Proceedings of the 32nd ACM Symposium on Parallelism in Algorithms and Architectures (SPAA 2020))
The Massively Parallel Computation (MPC) model is an emerging model which distills core aspects of distributed and parallel computation. It has been developed as a tool to solve (typically graph) problems in systems where the input is distributed over many machines with limited space. Recent work has focused on the regime in which machines have sublinear (in $n$, the number of nodes in the input graph) space, with randomized algorithms presented for fundamental graph problems of Maximal Matching and Maximal Independent Set. However, there have been no prior corresponding deterministic algorithms. A major challenge underlying the sublinear space setting is that the local space of each machine might be too small to store all the edges incident to a single node. This poses a considerable obstacle compared to the classical models in which each node is assumed to know and have easy access to its incident edges. To overcome this barrier we introduce a new graph sparsification technique that deterministically computes a low-degree subgraph with additional desired properties. The degree of the nodes in this subgraph is small in the sense that the edges of each node can be now stored on a single machine. This low-degree subgraph also has the property that solving the problem on this subgraph provides significant global progress, i.e., progress towards solving the problem for the original input graph. Using this framework to derandomize the well-known randomized algorithm of Luby [SICOMP'86], we obtain $O(\log Δ+\log\log n)$-round deterministic MPC algorithms for solving the fundamental problems of Maximal Matching and Maximal Independent Set with $O(n^{ε})$ space on each machine for any constant $ε > 0$. Based on the recent work of Ghaffari et al. [FOCS'18], this additive $O(\log\log n)$ factor is conditionally essential. These algorithms can also be shown to run in $O(\log Δ)$ rounds in the closely related model of CONGESTED CLIQUE, improving upon the state-of-the-art bound of $O(\log^2 Δ)$ rounds by Censor-Hillel et al. [DISC'17].

Non-blocking interpolation search trees with doubly-logarithmic running time - Brown, Trevor A; Prokopec, Aleksandar; Alistarh, Dan-Adrian (Proceedings of the ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming)
Balanced search trees typically use key comparisons to guide their operations, and achieve logarithmic running time. By relying on numerical properties of the keys, interpolation search achieves lower search complexity and better performance. Although interpolation-based data structures were investigated in the past, their non-blocking concurrent variants have received very little attention so far. In this paper, we propose the first non-blocking implementation of the classic interpolation search tree (IST) data structure. For arbitrary key distributions, the data structure ensures worst-case O(log n + p) amortized time for search, insertion and deletion traversals. When the input key distributions are smooth, lookups run in expected O(log log n + p) time, and insertion and deletion run in expected amortized O(log log n + p) time, where p is a bound on the number of threads. To improve the scalability of concurrent insertion and deletion, we propose a novel parallel rebuilding technique, which should be of independent interest. We evaluate whether the theoretical improvements translate to practice by implementing the concurrent interpolation search tree, and benchmarking it on uniform and nonuniform key distributions, for dataset sizes in the millions to billions of keys. Relative to the state-of-the-art concurrent data structures, the concurrent interpolation search tree achieves performance improvements of up to 15% under high update rates, and of up to 50% under moderate update rates. Further, ISTs exhibit up to 2X less cache-misses, and consume 1.2 -- 2.6X less memory compared to the next best alternative on typical dataset sizes. We find that the results are surprisingly robust to distributional skew, which suggests that our data structure can be a promising alternative to classic concurrent search structures.

Memory tagging: Minimalist synchronization for scalable concurrent data structures - Alistarh, Dan-Adrian; Brown, Trevor A; Singhal, Nandini (Annual ACM Symposium on Parallelism in Algorithms and Architectures)
There has been a significant amount of research on hardware and software support for efficient concurrent data structures; yet, the question of how to build correct, simple, and scalable data structures has not yet been definitively settled. In this paper, we revisit this question from a minimalist perspective, and ask: what is the smallest amount of synchronization required for correct and efficient concurrent search data structures, and how could this minimal synchronization support be provided in hardware? To address these questions, we introduce memory tagging, a simple hardware mechanism which enables the programmer to "tag" a dynamic set of memory locations, at cache-line granularity, and later validate whether the memory has been concurrently modified, with the possibility of updating one of the underlying locations atomically if validation succeeds. We provide several examples showing that this mechanism can enable fast and arguably simple concurrent data structure designs, such as lists, binary search trees, balanced search trees, range queries, and Software Transactional Memory (STM) implementations. We provide an implementation of memory tags in the Graphite multi-core simulator, showing that the mechanism can be implemented entirely at the level of L1 cache, and that it can enable non-trivial speedups versus existing implementations of the above data structures.

Testing concurrency on the JVM with Lincheck - Koval, Nikita; Sokolova, Mariia; Fedorov, Alexander; Alistarh, Dan-Adrian; Tsitelov, Dmitry (Proceedings of the ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming, PPOPP)
Concurrent programming can be notoriously complex and error-prone. Programming bugs can arise from a variety of sources, such as operation re-reordering, or incomplete understanding of the memory model. A variety of formal and model checking methods have been developed to address this fundamental difficulty. While technically interesting, existing academic methods are still hard to apply to the large codebases typical of industrial deployments, which limits their practical impact.

Brief Announcement: Why Extension-Based Proofs Fail - Alistarh, Dan-Adrian; Aspnes, James; Ellen, Faith; Gelashvili, Rati; Zhu, Leqi (Proceedings of the 39th Symposium on Principles of Distributed Computing)
We introduce extension-based proofs, a class of impossibility proofs that includes valency arguments. They are modelled as an interaction between a prover and a protocol. Using proofs based on combinatorial topology, it has been shown that it is impossible to deterministically solve k-set agreement among n > k ≥ 2 processes in a wait-free manner. However, it was unknown whether proofs based on simpler techniques were possible. We explain why this impossibility result cannot be obtained by an extension-based proof and, hence, extension-based proofs are limited in power.

Homogenized yarn-level cloth - Sperl, Georg; Narain, Rahul; Wojtan, Christopher J (ACM Transactions on Graphics)
We present a method for animating yarn-level cloth effects using a thin-shell solver. We accomplish this through numerical homogenization: we first use a large number of yarn-level simulations to build a model of the potential energy density of the cloth, and then use this energy density function to compute forces in a thin shell simulator. We model several yarn-based materials, including both woven and knitted fabrics. Our model faithfully reproduces expected effects like the stiffness of woven fabrics, and the highly deformable nature and anisotropy of knitted fabrics. Our approach does not require any real-world experiments nor measurements; because the method is based entirely on simulations, it can generate entirely new material models quickly, without the need for testing apparatuses or human intervention. We provide data-driven models of several woven and knitted fabrics, which can be used for efficient simulation with an off-the-shelf cloth solver.

Shear-induced ordering in systems with competing interactions: A machine learning study - Pȩkalski, J.; Rzadkowski, Wojciech; Panagiotopoulos, A. Z. (The Journal of chemical physics)
When short-range attractions are combined with long-range repulsions in colloidal particle systems, complex microphases can emerge. Here, we study a system of isotropic particles, which can form lamellar structures or a disordered fluid phase when temperature is varied. We show that, at equilibrium, the lamellar structure crystallizes, while out of equilibrium, the system forms a variety of structures at different shear rates and temperatures above melting. The shear-induced ordering is analyzed by means of principal component analysis and artificial neural networks, which are applied to data of reduced dimensionality. Our results reveal the possibility of inducing ordering by shear, potentially providing a feasible route to the fabrication of ordered lamellar structures from isotropic particles.

Effect of Zeeman coupling on the Majorana vortex modes in iron-based topological superconductors - Ghazaryan, Areg; Lopes, P. L.S.; Hosur, Pavan; Gilbert, Matthew J.; Ghaemi, Pouyan (Physical Review B)
In the superconducting regime of FeTe(1−x)Sex, there exist two types of vortices which are distinguished by the presence or absence of zero-energy states in their core. To understand their origin, we examine the interplay of Zeeman coupling and superconducting pairings in three-dimensional metals with band inversion. Weak Zeeman fields are found to suppress intraorbital spin-singlet pairing, known to localize the states at the ends of the vortices on the surface. On the other hand, an orbital-triplet pairing is shown to be stable against Zeeman interactions, but leads to delocalized zero-energy Majorana modes which extend through the vortex. In contrast, the finite-energy vortex modes remain localized at the vortex ends even when the pairing is of orbital-triplet form. Phenomenologically, this manifests as an observed disappearance of zero-bias peaks within the cores of topological vortices upon an increase of the applied magnetic field. The presence of magnetic impurities in FeTe(1−x)Sex, which are attracted to the vortices, would lead to such Zeeman-induced delocalization of Majorana modes in a fraction of vortices that capture a large enough number of magnetic impurities. Our results provide an explanation for the dichotomy between topological and nontopological vortices recently observed in FeTe(1−x)Sex.

Retrieval of cavity-generated atomic spin squeezing after free-space release - Wu, Yunfan; Krishnakumar, Rajiv; Martínez-Rincón, Julián; Malia, Benjamin K.; Hosten, Onur; Kasevich, Mark A. (Physical Review A)
We demonstrate that releasing atoms into free space from an optical lattice does not deteriorate cavity-generated spin squeezing for metrological purposes. In this work, an ensemble of 500000 spin-squeezed atoms in a high-finesse optical cavity with near-uniform atom-cavity coupling is prepared, released into free space, recaptured in the cavity, and probed. Up to ∼10 dB of metrologically relevant squeezing is retrieved for 700μs free-fall times, and decaying levels of squeezing are realized for up to 3 ms free-fall times. The degradation of squeezing results from loss of atom-cavity coupling homogeneity between the initial squeezed state generation and final collective state readout. A theoretical model is developed to quantify this degradation and this model is experimentally validated.

Making procedural water waves boundary-aware - Jeschke, Stefan; Hafner, Christian; Chentanez, Nuttapong; Macklin, Miles; Müller-Fischer, Matthias; Wojtan, Christopher J (Computer Graphics forum)
The “procedural” approach to animating ocean waves is the dominant algorithm for animating larger bodies of water in interactive applications as well as in off-line productions — it provides high visual quality with a low computational demand. In this paper, we widen the applicability of procedural water wave animation with an extension that guarantees the satisfaction of boundary conditions imposed by terrain while still approximating physical wave behavior. In combination with a particle system that models wave breaking, foam, and spray, this allows us to naturally model waves interacting with beaches and rocks. Our system is able to animate waves at large scales at interactive frame rates on a commodity PC.

Reinforcement learning of risk-constrained policies in Markov decision processes - Brázdil, Tomáš; Chatterjee, Krishnendu; Novotný, Petr; Vahala, Jiří (Proceedings of the 34th AAAI Conference on Artificial Intelligence)
Markov decision processes (MDPs) are the defacto framework for sequential decision making in the presence of stochastic uncertainty. A classical optimization criterion for MDPs is to maximize the expected discounted-sum payoff, which ignores low probability catastrophic events with highly negative impact on the system. On the other hand, risk-averse policies require the probability of undesirable events to be below a given threshold, but they do not account for optimization of the expected payoff. We consider MDPs with discounted-sum payoff with failure states which represent catastrophic outcomes. The objective of risk-constrained planning is to maximize the expected discounted-sum payoff among risk-averse policies that ensure the probability to encounter a failure state is below a desired threshold. Our main contribution is an efficient risk-constrained planning algorithm that combines UCT-like search with a predictor learned through interaction with the MDP (in the style of AlphaZero) and with a risk-constrained action selection via linear programming. We demonstrate the effectiveness of our approach with experiments on classical MDPs from the literature, including benchmarks with an order of 106 states.
Keywords: General Medicine

VRK-1 extends life span by activation of AMPK via phosphorylation - Park, Sangsoon; Artan, Murat; Han, Seung Hyun; Park, Hae-Eun H.; Jung, Yoonji; Hwang, Ara B.; Shin, Won Sik; Kim, Kyong-Tai; Lee, Seung-Jae V. (Science Advances)
Vaccinia virus–related kinase (VRK) is an evolutionarily conserved nuclear protein kinase. VRK-1, the single Caenorhabditis elegans VRK ortholog, functions in cell division and germline proliferation. However, the role of VRK-1 in postmitotic cells and adult life span remains unknown. Here, we show that VRK-1 increases organismal longevity by activating the cellular energy sensor, AMP-activated protein kinase (AMPK), via direct phosphorylation. We found that overexpression of vrk-1 in the soma of adult C. elegans increased life span and, conversely, inhibition of vrk-1 decreased life span. In addition, vrk-1 was required for longevity conferred by mutations that inhibit C. elegans mitochondrial respiration, which requires AMPK. VRK-1 directly phosphorylated and up-regulated AMPK in both C. elegans and cultured human cells. Thus, our data show that the somatic nuclear kinase, VRK-1, promotes longevity through AMPK activation, and this function appears to be conserved between C. elegans and humans.

Calcium modulates the domain flexibility and function of an α-actinin similar to the ancestral α-actinin - Pinotsis, Nikos; Zielinska, Karolina; Babuta, Mrigya; Arolas, Joan L.; Kostan, Julius; Khan, Muhammad Bashir; Schreiner, Claudia; Testa Salmazo, Anita P; Ciccarelli, Luciano; Puchinger, Martin; Gkougkoulia, Eirini A.; Ribeiro, Euripedes de Almeida; et al. (Proceedings of the National Academy of Sciences)
The actin cytoskeleton, a dynamic network of actin filaments and associated F-actin–binding proteins, is fundamentally important in eukaryotes. α-Actinins are major F-actin bundlers that are inhibited by Ca2+ in nonmuscle cells. Here we report the mechanism of Ca2+-mediated regulation of Entamoeba histolytica α-actinin-2 (EhActn2) with features expected for the common ancestor of Entamoeba and higher eukaryotic α-actinins. Crystal structures of Ca2+-free and Ca2+-bound EhActn2 reveal a calmodulin-like domain (CaMD) uniquely inserted within the rod domain. Integrative studies reveal an exceptionally high affinity of the EhActn2 CaMD for Ca2+, binding of which can only be regulated in the presence of physiological concentrations of Mg2+. Ca2+ binding triggers an increase in protein multidomain rigidity, reducing conformational flexibility of F-actin–binding domains via interdomain cross-talk and consequently inhibiting F-actin bundling. In vivo studies uncover that EhActn2 plays an important role in phagocytic cup formation and might constitute a new drug target for amoebic dysentery.

Čech-Delaunay gradient flow and homology inference for self-maps - Bauer, U.; Edelsbrunner, Herbert; Jablonski, Grzegorz; Mrozek, M. (Journal of Applied and Computational Topology)
We call a continuous self-map that reveals itself through a discrete set of point-value pairs a sampled dynamical system. Capturing the available information with chain maps on Delaunay complexes, we use persistent homology to quantify the evidence of recurrent behavior. We establish a sampling theorem to recover the eigenspaces of the endomorphism on homology induced by the self-map. Using a combinatorial gradient flow arising from the discrete Morse theory for Čech and Delaunay complexes, we construct a chain map to transform the problem from the natural but expensive Čech complexes to the computationally efficient Delaunay triangulations. The fast chain map algorithm has applications beyond dynamical systems.

Optimal lower bound on the least singular value of the shifted Ginibre ensemble - Cipolloni, Giorgio; Erdös, László; Schröder, Dominik J (Probability and Mathematical Physics)
We consider the least singular value of a large random matrix with real or complex i.i.d. Gaussian entries shifted by a constant z∈C. We prove an optimal lower tail estimate on this singular value in the critical regime where z is around the spectral edge, thus improving the classical bound of Sankar, Spielman and Teng (SIAM J. Matrix Anal. Appl. 28:2 (2006), 446–476) for the particular shift-perturbation in the edge regime. Lacking Brézin–Hikami formulas in the real case, we rely on the superbosonization formula (Comm. Math. Phys. 283:2 (2008), 343–395).
Keywords: General Medicine

Compact millimeter and submillimeter-wave photonic radiometer for cubesats - Wasiak, Michal; Botello, Gabriel Santamaria; Abdalmalak, Kerlos Atia; Sedlmeir, Florian; Rueda Sanchez, Alfredo R; Segovia-Vargas, Daniel; Schwefel, Harald G. L.; Munoz, Luis Enrique Garcia (14th European Conference on Antennas and Propagation)
In this paper we present a room temperature radiometer that can eliminate the need of using cryostats in satellite payload reducing its weight and improving reliability. The proposed radiometer is based on an electro-optic upconverter that boosts up microwave photons energy by upconverting them into an optical domain what makes them immune to thermal noise even if operating at room temperature. The converter uses a high-quality factor whispering gallery mode (WGM) resonator providing naturally narrow bandwidth and therefore might be useful for applications like microwave hyperspectral sensing. The upconversion process is explained by providing essential information about photon conversion efficiency and sensitivity. To prove the concept, we describe an experiment which shows state-of-the-art photon conversion efficiency n=10-5 per mW of pump power at the frequency of 80 GHz.

Brief announcement: Efficient load-balancing through distributed token dropping - Brandt, Sebastian; Keller, Barbara; Rybicki, Joel; Suomela, Jukka; Uitto, Jara (34th International Symposium on Distributed Computing)
We introduce a new graph problem, the token dropping game, and we show how to solve it efficiently in a distributed setting. We use the token dropping game as a tool to design an efficient distributed algorithm for the stable orientation problem, which is a special case of the more general locally optimal semi-matching problem. The prior work by Czygrinow et al. (DISC 2012) finds a locally optimal semi-matching in O(Δ⁵) rounds in graphs of maximum degree Δ, which directly implies an algorithm with the same runtime for stable orientations. We improve the runtime to O(Δ⁴) for stable orientations and prove a lower bound of Ω(Δ) rounds.

Dynamic averaging load balancing on cycles - Alistarh, Dan-Adrian; Nadiradze, Giorgi; Sabour, Amirmojtaba (47th International Colloquium on Automata, Languages, and Programming)
We consider the following dynamic load-balancing process: given an underlying graph G with n nodes, in each step t≥ 0, one unit of load is created, and placed at a randomly chosen graph node. In the same step, the chosen node picks a random neighbor, and the two nodes balance their loads by averaging them. We are interested in the expected gap between the minimum and maximum loads at nodes as the process progresses, and its dependence on n and on the graph structure. Variants of the above graphical balanced allocation process have been studied previously by Peres, Talwar, and Wieder [Peres et al., 2015], and by Sauerwald and Sun [Sauerwald and Sun, 2015]. These authors left as open the question of characterizing the gap in the case of cycle graphs in the dynamic case, where weights are created during the algorithm’s execution. For this case, the only known upper bound is of 𝒪(n log n), following from a majorization argument due to [Peres et al., 2015], which analyzes a related graphical allocation process. In this paper, we provide an upper bound of 𝒪 (√n log n) on the expected gap of the above process for cycles of length n. We introduce a new potential analysis technique, which enables us to bound the difference in load between k-hop neighbors on the cycle, for any k ≤ n/2. We complement this with a "gap covering" argument, which bounds the maximum value of the gap by bounding its value across all possible subsets of a certain structure, and recursively bounding the gaps within each subset. We provide analytical and experimental evidence that our upper bound on the gap is tight up to a logarithmic factor.

Disjoint tree-compatible plane perfect matchings - Aichholzer, Oswin; Obmann, Julia; Patak, Pavel; Perz, Daniel; Tkadlec, Josef (36th European Workshop on Computational Geometry)
Two plane drawings of geometric graphs on the same set of points are called disjoint compatible if their union is plane and they do not have an edge in common. For a given set S of 2n points two plane drawings of perfect matchings M1 and M2 (which do not need to be disjoint nor compatible) are disjoint tree-compatible if there exists a plane drawing of a spanning tree T on S which is disjoint compatible to both M1 and M2. We show that the graph of all disjoint tree-compatible perfect geometric matchings on 2n points in convex position is connected if and only if 2n ≥ 10. Moreover, in that case the diameter of this graph is either 4 or 5, independent of n.

Analysis of a two-layer neural network via displacement convexity - Javanmard, Adel; Mondelli, Marco; Montanari, Andrea (Annals of Statistics)
Fitting a function by using linear combinations of a large number N of `simple' components is one of the most fruitful ideas in statistical learning. This idea lies at the core of a variety of methods, from two-layer neural networks to kernel regression, to boosting. In general, the resulting risk minimization problem is non-convex and is solved by gradient descent or its variants. Unfortunately, little is known about global convergence properties of these approaches. Here we consider the problem of learning a concave function f on a compact convex domain Ω⊆ℝd, using linear combinations of `bump-like' components (neurons). The parameters to be fitted are the centers of N bumps, and the resulting empirical risk minimization problem is highly non-convex. We prove that, in the limit in which the number of neurons diverges, the evolution of gradient descent converges to a Wasserstein gradient flow in the space of probability distributions over Ω. Further, when the bump width δ tends to 0, this gradient flow has a limit which is a viscous porous medium equation. Remarkably, the cost function optimized by this gradient flow exhibits a special property known as displacement convexity, which implies exponential convergence rates for N→∞, δ→0. Surprisingly, this asymptotic theory appears to capture well the behavior for moderate values of δ,N. Explaining this phenomenon, and understanding the dependence on δ,N in a quantitative manner remains an outstanding challenge.

Geometry and physics of Higgs bundles - Anderson, Lara; Hausel, Tamás; Mazzeo, Rafe; Schaposnik, Laura (Oberwolfach Reports)
This workshop focused on interactions between the various perspectives on the moduli space of Higgs bundles over a Riemann surface. This subject draws on algebraic geometry, geometric topology, geometric analysis and mathematical physics, and the goal was to promote interactions between these various branches of the subject. The main current directions of research were well represented by the participants, and the talks included many from both senior and junior participants.
Keywords: Organic Chemistry; Biochemistry

Emergence of cascading dynamics in interacting tipping elements of ecology and climate: Cascading dynamics in tipping elements - Klose, Ann Kristin; Karle, Volker; Winkelmann, Ricarda; Donges, Jonathan F. (Royal Society Open Science)
In ecology, climate and other fields, (sub)systems have been identified that can transition into a qualitatively different state when a critical threshold or tipping point in a driving process is crossed. An understanding of those tipping elements is of great interest given the increasing influence of humans on the biophysical Earth system. Complex interactions exist between tipping elements, e.g. physical mechanisms connect subsystems of the climate system. Based on earlier work on such coupled nonlinear systems, we systematically assessed the qualitative long-term behaviour of interacting tipping elements. We developed an understanding of the consequences of interactions on the tipping behaviour allowing for tipping cascades to emerge under certain conditions. The (narrative) application of these qualitative results to real-world examples of interacting tipping elements indicates that tipping cascades with profound consequences may occur: the interacting Greenland ice sheet and thermohaline ocean circulation might tip before the tipping points of the isolated subsystems are crossed. The eutrophication of the first lake in a lake chain might propagate through the following lakes without a crossing of their individual critical nutrient input levels. The possibility of emerging cascading tipping dynamics calls for the development of a unified theory of interacting tipping elements and the quantitative analysis of interacting real-world tipping elements.

Random matrices - Erdös, László; Götze, Friedrich; Guionnet, Alice (Oberwolfach Reports)
Large complex systems tend to develop universal patterns that often represent their essential characteristics. For example, the cumulative effects of independent or weakly dependent random variables often yield the Gaussian universality class via the central limit theorem. For non-commutative random variables, e.g. matrices, the Gaussian behavior is often replaced by another universality class, commonly called random matrix statistics. Nearby eigenvalues are strongly correlated, and, remarkably, their correlation structure is universal, depending only on the symmetry type of the matrix. Even more surprisingly, this feature is not restricted to matrices; in fact Eugene Wigner, the pioneer of the field, discovered in the 1950s that distributions of the gaps between energy levels of complicated quantum systems universally follow the same random matrix statistics. This claim has never been rigorously proved for any realistic physical system but experimental data and extensive numerics leave no doubt as to its correctness. Since then random matrices have proved to be extremely useful phenomenological models in a wide range of applications beyond quantum physics that include number theory, statistics, neuroscience, population dynamics, wireless communication and mathematical finance. The ubiquity of random matrices in natural sciences is still a mystery, but recent years have witnessed a breakthrough in the mathematical description of the statistical structure of their spectrum. Random matrices and closely related areas such as log-gases have become an extremely active research area in probability theory. This workshop brought together outstanding researchers from a variety of mathematical backgrounds whose areas of research are linked to random matrices. While there are strong links between their motivations, the techniques used by these researchers span a large swath of mathematics, ranging from purely algebraic techniques to stochastic analysis, classical probability theory, operator algebra, supersymmetry, orthogonal polynomials, etc.

Many-body quantum systems - Hainzl, Christian; Schlein, Benjamin; Seiringer, Robert; Warzel, Simone (Oberwolfach Reports)
The interaction among fundamental particles in nature leads to many interesting effects in quantum statistical mechanics; examples include superconductivity for charged systems and superfluidity in cold gases. It is a huge challenge for mathematical physics to understand the collective behavior of systems containing a large number of particles, emerging from known microscopic interactions. In this workshop we brought together researchers working on different aspects of many-body quantum mechanics to discuss recent developments, exchange ideas and propose new challenges and research directions.

Characterization of methanosarcina mazei JL01 isolated from holocene arctic permafrost and study of the archaeon cooperation with bacterium Sphaerochaeta associata GLS2T - Oshurkova, Viktoriia; Troshina, Olga; Trubitsyn, Vladimir; Ryzhmanova, Yana; Bochkareva, Olga; Shcherbakova, Viktoria (Proceedings of 1st International Electronic Conference on Microbiology)
A mesophilic methanogenic culture, designated JL01, was isolated from Holocene permafrost in the Russian Arctic [1]. After long-term extensive cultivation at 15°C it turned out to be a tied binary culture of archaeal (JL01) and bacterial (Sphaerochaeta associata GLS2) strains. Strain JL01 was a strict anaerobe and grew on methanol, acetate and methylamines as energy and carbon sources. Cells were irregular coccoid, non-motile, non-spore-forming, and Gram-stainpositive. Optimum conditions for growth were 24-28 oC, pH 6.8–7.3 and 0.075-0.1 M NaCl. Phylogenetic tree reconstructions based on 16S rRNA and concatenated alignment of broadly conserved protein-coding genes revealed its close relation to Methanosarcina mazei S-6 T (similarity 99.5%). The comparison of whole genomic sequences (ANI) of the isolate and the type strain of M.mazei was 98.5%, which is higher than the values recommended for new species. Thus strain JL01 (=VKM B-2370=JCM 31898) represents the first M. mazei isolated from permanently subzero Arcticsediments. The long-term co-cultivation of JL01 with S. associata GLS2T showed the methane production without any additional carbon and energy sources. Genome analysis of S. associata GLS2T revealed putative genes involved in methanochondroithin catabolism.

Cryo-electron tomography workflows for quantitative analysis of actin networks involved in cell migration - Fäßler, Florian; Dimchev, Georgi A; Hodirnau, Victor-Valentin; Zens, Bettina; Möhl, Christoph; Bradke, Frank; Schur, Florian KM (Microscopy and Microanalysis)
Keywords: Instrumentation

Adaptive gradient quantization for data-parallel SGD - Faghri, Fartash; Tabrizian, Iman; Markov, Ilia; Alistarh, Dan-Adrian; Roy, Daniel; Ramezani-Kebrya, Ali (Advances in Neural Information Processing Systems)
Many communication-efficient variants of SGD use gradient quantization schemes. These schemes are often heuristic and fixed over the course of training. We empirically observe that the statistics of gradients of deep models change during the training. Motivated by this observation, we introduce two adaptive quantization schemes, ALQ and AMQ. In both schemes, processors update their compression schemes in parallel by efficiently computing sufficient statistics of a parametric distribution. We improve the validation accuracy by almost 2% on CIFAR-10 and 1% on ImageNet in challenging low-cost communication setups. Our adaptive methods are also significantly more robust to the choice of hyperparameters.

Localization and functional role of Cav2.3 in the medial habenula to interpeduncular nucleus pathway - Bhandari, Pradeep
The medial habenula (MHb) is an evolutionary conserved epithalamic structure important for the modulation of emotional memory. It is involved in regulation of anxiety, compulsive behavior, addiction (nicotinic and opioid), sexual and feeding behavior. MHb receives inputs from septal regions and projects exclusively to the interpeduncular nucleus (IPN). Distinct sub-regions of the septum project to different subnuclei of MHb: the bed nucleus of anterior commissure projects to dorsal MHb and the triangular septum projects to ventral MHb. Furthermore, the dorsal and ventral MHb project to the lateral and rostral/central IPN, respectively. Importantly, these projections have unique features of prominent co-release of different neurotransmitters and requirement of a peculiar type of calcium channel for release. In general, synaptic neurotransmission requires an activity-dependent influx of Ca2+ into the presynaptic terminal through voltage-gated calcium channels. The calcium channel family most commonly involved in neurotransmitter release comprises three members, P/Q-, N- and R-type with Cav2.1, Cav2.2 and Cav2.3 subunits, respectively. In contrast to most CNS synapses that mainly express Cav2.1 and/or Cav2.2, MHb terminals in the IPN exclusively express Cav2.3. In other parts of the brain, such as the hippocampus, Cav2.3 is mostly located to postsynaptic elements. This unusual presynaptic location of Cav2.3 in the MHb-IPN pathway implies unique mechanisms of glutamate release in this pathway. One potential example of such uniqueness is the facilitation of release by GABAB receptor (GBR) activation. Presynaptic GBRs usually inhibit the release of neurotransmitters by inhibiting presynaptic calcium channels. MHb shows the highest expression levels of GBR in the brain. GBRs comprise two subunits, GABAB1 (GB1) and GABAB2 (GB2), and are associated with auxiliary subunits, called potassium channel tetramerization domain containing proteins (KCTD) 8, 12, 12b and 16. Among these four subunits, KCTD12b is exclusively expressed in ventral MHb, and KCTD8 shows the strongest expression in the whole MHb among other brain regions, indicating that KCTD8 and KCTD12b may be involved in the unique mechanisms of neurotransmitter release mediated by Cav2.3 and regulated by GBRs in this pathway. In the present study, we first verified that neurotransmission in both dorsal and ventral MHb-IPN pathways is mainly mediated by Cav2.3 using a selective blocker of R-type channels, SNX-482. We next found that baclofen, a GBR agonist, has facilitatory effects on release from ventral MHb terminal in rostral IPN, whereas it has inhibitory effects on release from dorsal MHb terminals in lateral IPN, indicating that KCTD12b expressed exclusively in ventral MHb may have a role in the facilitatory effects of GBR activation. In a heterologous expression system using HEK cells, we found that KCTD8 and KCTD12b but not KCTD12 directly bind with Cav2.3. Pre-embedding immunogold electron microscopy data show that Cav2.3 and KCTD12b are distributed most densely in presynaptic active zone in IPN with KCTD12b being present only in rostral/central but not lateral IPN, whereas GABAB, KCTD8 and KCTD12 are distributed most densely in perisynaptic sites with KCTD12 present more frequently in postsynaptic elements and only in rostral/central IPN. In freeze-fracture replica labelling, Cav2.3, KCTD8 and KCTD12b are co-localized with each other in the same active zone indicating that they may form complexes regulating vesicle release in rostral IPN. On electrophysiological studies of wild type (WT) mice, we found that paired-pulse ratio in rostral IPN of KCTD12b knock-out (KO) mice is lower than those of WT and KCTD8 KO mice. Consistent with this finding, in mean variance analysis, release probability in rostral IPN of KCTD12b KO mice is higher than that of WT and KCTD8 KO mice. Although paired-pulse ratios are not different between WT and KCTD8 KO mice, the mean variance analysis revealed significantly lower release probability in rostral IPN of KCTD8 KO than WT mice. These results demonstrate bidirectional regulation of Cav2.3-mediated release by KCTD8 and KCTD12b without GBR activation in rostral IPN. Finally, we examined the baclofen effects in rostral IPN of KCTD8 and KCTD12b KO mice, and found the facilitation of release remained in both KO mice, indicating that the peculiar effects of the GBR activation in this pathway do not depend on the selective expression of these KCTD subunits in ventral MHb. However, we found that presynaptic potentiation of evoked EPSC amplitude by baclofen falls to baseline after washout faster in KCTD12b KO mice than WT, KCTD8 KO and KCTD8/12b double KO mice. This result indicates that KCTD12b is involved in sustained potentiation of vesicle release by GBR activation, whereas KCTD8 is involved in its termination in the absence of KCTD12b. Consistent with these functional findings, replica labelling revealed an increase in density of KCTD8, but not Cav2.3 or GBR at active zone in rostral IPN of KCTD12b KO mice compared with that of WT mice, suggesting that increased association of KCTD8 with Cav2.3 facilitates the release probability and termination of the GBR effect in the absence of KCTD12b. In summary, our study provided new insights into the physiological roles of presynaptic Cav2.3, GBRs and their auxiliary subunits KCTDs at an evolutionary conserved neuronal circuit. Future studies will be required to identify the exact molecular mechanism underlying the GBR-mediated presynaptic potentiation on ventral MHb terminals. It remains to be determined whether the prominent presence of presynaptic KCTDs at active zone could exert similar neuromodulatory functions in different pathways of the brain.
Keywords: Cav2.3; medial habenula (MHb); interpeduncular nucleus (IPN)

3D printed cell culture grid holders for improved cellular specimen preparation in cryo-electron microscopy - Fäßler, Florian; Zens, Bettina; Hauschild, Robert; Schur, Florian KM (Journal of Structural Biology)
Cryo-electron microscopy (cryo-EM) of cellular specimens provides insights into biological processes and structures within a native context. However, a major challenge still lies in the efficient and reproducible preparation of adherent cells for subsequent cryo-EM analysis. This is due to the sensitivity of many cellular specimens to the varying seeding and culturing conditions required for EM experiments, the often limited amount of cellular material and also the fragility of EM grids and their substrate. Here, we present low-cost and reusable 3D printed grid holders, designed to improve specimen preparation when culturing challenging cellular samples directly on grids. The described grid holders increase cell culture reproducibility and throughput, and reduce the resources required for cell culturing. We show that grid holders can be integrated into various cryo-EM workflows, including micro-patterning approaches to control cell seeding on grids, and for generating samples for cryo-focused ion beam milling and cryo-electron tomography experiments. Their adaptable design allows for the generation of specialized grid holders customized to a large variety of applications.
Keywords: electron microscopy; cryo-EM; EM sample preparation; 3D printing; cell culture

Functional electron microscopy (“Flash and Freeze”) of identified cortical synapses in acute brain slices - Borges Merjane, Carolina; Kim, Olena; Jonas, Peter M (Neuron)
How structural and functional properties of synapses relate to each other is a fundamental question in neuroscience. Electrophysiology has elucidated mechanisms of synaptic transmission, and electron microscopy (EM) has provided insight into morphological properties of synapses. Here we describe an enhanced method for functional EM (“flash and freeze”), combining optogenetic stimulation with high-pressure freezing. We demonstrate that the improved method can be applied to intact networks in acute brain slices and organotypic slice cultures from mice. As a proof of concept, we probed vesicle pool changes during synaptic transmission at the hippocampal mossy fiber-CA3 pyramidal neuron synapse. Our findings show overlap of the docked vesicle pool and the functionally defined readily releasable pool and provide evidence of fast endocytosis at this synapse. Functional EM with acute slices and slice cultures has the potential to reveal the structural and functional mechanisms of transmission in intact, genetically perturbed, and disease-affected synapses.

Perturbations of protein synthesis: from antibiotics to genetics and physiology - Kavcic, Bor
Synthesis of proteins – translation – is a fundamental process of life. Quantitative studies anchor translation into the context of bacterial physiology and reveal several mathematical relationships, called “growth laws,” which capture physiological feedbacks between protein synthesis and cell growth. Growth laws describe the dependency of the ribosome abundance as a function of growth rate, which can change depending on the growth conditions. Perturbations of translation reveal that bacteria employ a compensatory strategy in which the reduced translation capability results in increased expression of the translation machinery. Perturbations of translation are achieved in various ways; clinically interesting is the application of translation-targeting antibiotics – translation inhibitors. The antibiotic effects on bacterial physiology are often poorly understood. Bacterial responses to two or more simultaneously applied antibiotics are even more puzzling. The combined antibiotic effect determines the type of drug interaction, which ranges from synergy (the effect is stronger than expected) to antagonism (the effect is weaker) and suppression (one of the drugs loses its potency). In the first part of this work, we systematically measure the pairwise interaction network for translation inhibitors that interfere with different steps in translation. We find that the interactions are surprisingly diverse and tend to be more antagonistic. To explore the underlying mechanisms, we begin with a minimal biophysical model of combined antibiotic action. We base this model on the kinetics of antibiotic uptake and binding together with the physiological response described by the growth laws. The biophysical model explains some drug interactions, but not all; it specifically fails to predict suppression. In the second part of this work, we hypothesize that elusive suppressive drug interactions result from the interplay between ribosomes halted in different stages of translation. To elucidate this putative mechanism of drug interactions between translation inhibitors, we generate translation bottlenecks genetically using in- ducible control of translation factors that regulate well-defined translation cycle steps. These perturbations accurately mimic antibiotic action and drug interactions, supporting that the interplay of different translation bottlenecks partially causes these interactions. We extend this approach by varying two translation bottlenecks simultaneously. This approach reveals the suppression of translocation inhibition by inhibited translation. We rationalize this effect by modeling dense traffic of ribosomes that move on transcripts in a translation factor-mediated manner. This model predicts a dissolution of traffic jams caused by inhibited translocation when the density of ribosome traffic is reduced by lowered initiation. We base this model on the growth laws and quantitative relationships between different translation and growth parameters. In the final part of this work, we describe a set of tools aimed at quantification of physiological and translation parameters. We further develop a simple model that directly connects the abundance of a translation factor with the growth rate, which allows us to extract physiological parameters describing initiation. We demonstrate the development of tools for measuring translation rate. This thesis showcases how a combination of high-throughput growth rate mea- surements, genetics, and modeling can reveal mechanisms of drug interactions. Furthermore, by a gradual transition from combinations of antibiotics to precise genetic interventions, we demonstrated the equivalency between genetic and chemi- cal perturbations of translation. These findings tile the path for quantitative studies of antibiotic combinations and illustrate future approaches towards the quantitative description of translation.

Zebrafish embryonic explants undergo genetically encoded self-assembly - Schauer, Alexandra; Nunes Pinheiro, Diana C; Hauschild, Robert; Heisenberg, Carl-Philipp J (eLife)
Embryonic stem cell cultures are thought to self-organize into embryoid bodies, able to undergo symmetry-breaking, germ layer specification and even morphogenesis. Yet, it is unclear how to reconcile this remarkable self-organization capacity with classical experiments demonstrating key roles for extrinsic biases by maternal factors and/or extraembryonic tissues in embryogenesis. Here, we show that zebrafish embryonic tissue explants, prepared prior to germ layer induction and lacking extraembryonic tissues, can specify all germ layers and form a seemingly complete mesendoderm anlage. Importantly, explant organization requires polarized inheritance of maternal factors from dorsal-marginal regions of the blastoderm. Moreover, induction of endoderm and head-mesoderm, which require peak Nodal-signaling levels, is highly variable in explants, reminiscent of embryos with reduced Nodal signals from the extraembryonic tissues. Together, these data suggest that zebrafish explants do not undergo bona fide self-organization, but rather display features of genetically encoded self-assembly, where intrinsic genetic programs control the emergence of order.

Mechanisms of drug interactions between translation-inhibiting antibiotics - Kavcic, Bor; Tkačik, Gašper; Bollenbach, Tobias (Nature Communications)
Antibiotics that interfere with translation, when combined, interact in diverse and difficult-to-predict ways. Here, we explain these interactions by “translation bottlenecks”: points in the translation cycle where antibiotics block ribosomal progression. To elucidate the underlying mechanisms of drug interactions between translation inhibitors, we generate translation bottlenecks genetically using inducible control of translation factors that regulate well-defined translation cycle steps. These perturbations accurately mimic antibiotic action and drug interactions, supporting that the interplay of different translation bottlenecks causes these interactions. We further show that growth laws, combined with drug uptake and binding kinetics, enable the direct prediction of a large fraction of observed interactions, yet fail to predict suppression. However, varying two translation bottlenecks simultaneously supports that dense traffic of ribosomes and competition for translation factors account for the previously unexplained suppression. These results highlight the importance of “continuous epistasis” in bacterial physiology.

A minimal biophysical model of combined antibiotic action - Kavcic, Bor; Tkačik, Gašper; Bollenbach, Tobias (bioRxiv)
Combining drugs can improve the efficacy of treatments. However, predicting the effect of drug combinations is still challenging. The combined potency of drugs determines the drug interaction, which is classified as synergistic, additive, antagonistic, or suppressive. While probabilistic, non-mechanistic models exist, there is currently no biophysical model that can predict antibiotic interactions. Here, we present a physiologically relevant model of the combined action of antibiotics that inhibit protein synthesis by targeting the ribosome. This model captures the kinetics of antibiotic binding and transport, and uses bacterial growth laws to predict growth in the presence of antibiotic combinations. We find that this biophysical model can produce all drug interaction types except suppression. We show analytically that antibiotics which cannot bind to the ribosome simultaneously generally act as substitutes for one another, leading to additive drug interactions. Previously proposed null expectations for higher-order drug interactions follow as a limiting case of our model. We further extend the model to include the effects of direct physical or allosteric interactions between individual drugs on the ribosome. Notably, such direct interactions profoundly change the combined drug effect, depending on the kinetic parameters of the drugs used. The model makes additional predictions for the effects of resistance genes on drug interactions and for interactions between ribosome-targeting antibiotics and antibiotics with other targets. These findings enhance our understanding of the interplay between drug action and cell physiology and are a key step toward a general framework for predicting drug interactions.

Wounding-induced changes in cellular pressure and localized auxin signalling spatially coordinate restorative divisions in roots - Hörmayer, Lukas; Montesinos López, Juan C; Marhavá, Petra; Benková, Eva; Yoshida, Saiko; Friml, Jiří (Proceedings of the National Academy of Sciences)
Wound healing in plant tissues, consisting of rigid cell wall-encapsulated cells, represents a considerable challenge and occurs through largely unknown mechanisms distinct from those in animals. Owing to their inability to migrate, plant cells rely on targeted cell division and expansion to regenerate wounds. Strict coordination of these wound-induced responses is essential to ensure efficient, spatially restricted wound healing. Single-cell tracking by live imaging allowed us to gain mechanistic insight into the wound perception and coordination of wound responses after laser-based wounding in Arabidopsis root. We revealed a crucial contribution of the collapse of damaged cells in wound perception and detected an auxin increase specific to cells immediately adjacent to the wound. This localized auxin increase balances wound-induced cell expansion and restorative division rates in a dose-dependent manner, leading to tumorous overproliferation when the canonical TIR1 auxin signaling is disrupted. Auxin and wound-induced turgor pressure changes together also spatially define the activation of key components of regeneration, such as the transcription regulator ERF115. Our observations suggest that the wound signaling involves the sensing of collapse of damaged cells and a local auxin signaling activation to coordinate the downstream transcriptional responses in the immediate wound vicinity.

Synthetic tools for optogenetic and chemogenetic inhibition of cellular signals - Kainrath, Stephanie
Proteins and their complex dynamic interactions regulate cellular mechanisms from sensing and transducing extracellular signals, to mediating genetic responses, and sustaining or changing cell morphology. To manipulate these protein-protein interactions (PPIs) that govern the behavior and fate of cells, synthetically constructed, genetically encoded tools provide the means to precisely target proteins of interest (POIs), and control their subcellular localization and activity in vitro and in vivo. Ideal synthetic tools react to an orthogonal cue, i.e. a trigger that does not activate any other endogenous process, thereby allowing manipulation of the POI alone. In optogenetics, naturally occurring photosensory domain from plants, algae and bacteria are re-purposed and genetically fused to POIs. Illumination with light of a specific wavelength triggers a conformational change that can mediate PPIs, such as dimerization or oligomerization. By using light as a trigger, these tools can be activated with high spatial and temporal precision, on subcellular and millisecond scales. Chemogenetic tools consist of protein domains that recognize and bind small molecules. By genetic fusion to POIs, these domains can mediate PPIs upon addition of their specific ligands, which are often synthetically designed to provide highly specific interactions and exhibit good bioavailability. Most optogenetic tools to mediate PPIs are based on well-studied photoreceptors responding to red, blue or near-UV light, leaving a striking gap in the green band of the visible light spectrum. Among both optogenetic and chemogenetic tools, there is an abundance of methods to induce PPIs, but tools to disrupt them require UV illumination, rely on covalent linkage and subsequent enzymatic cleavage or initially result in protein clustering of unknown stoichiometry. This work describes how the recently structurally and photochemically characterized green-light responsive cobalamin-binding domains (CBDs) from bacterial transcription factors were re-purposed to function as a green-light responsive optogenetic tool. In contrast to previously engineered optogenetic tools, CBDs do not induce PPI, but rather confer a PPI already upon expression, which can be rapidly disrupted by illumination. This was employed to mimic inhibition of constitutive activity of a growth factor receptor, and successfully implement for cell signalling in mammalian cells and in vivo to rescue development in zebrafish. This work further describes the development and application of a chemically induced de-dimerizer (CDD) based on a recently identified and structurally described bacterial oxyreductase. CDD forms a dimer upon expression in absence of its cofactor, the flavin derivative F420. Safety and of domain expression and ligand exposure are demonstrated in vitro and in vivo in zebrafish. The system is further applied to inhibit cell signalling output from a chimeric receptor upon F420 treatment. CBDs and CDD expand the repertoire of synthetic tools by providing novel mechanisms of mediating PPIs, and by recognizing previously not utilized cues. In the future, they can readily be combined with existing synthetic tools to functionally manipulate PPIs in vitro and in vivo.

Illuminating the role of Cul3 in autism spectrum disorder pathogenesis - Morandell, Jasmin
The development of the human brain occurs through a tightly regulated series of dynamic and adaptive processes during prenatal and postnatal life. A disruption of this strictly orchestrated series of events can lead to a number of neurodevelopmental conditions, including Autism Spectrum Disorders (ASDs). ASDs are a very common, etiologically and phenotypically heterogeneous group of disorders sharing the core symptoms of social interaction and communication deficits and restrictive and repetitive interests and behaviors. They are estimated to affect one in 59 individuals in the U.S. and, over the last three decades, mutations in more than a hundred genetic loci have been convincingly linked to ASD pathogenesis. Yet, for the vast majority of these ASD-risk genes their role during brain development and precise molecular function still remain elusive. De novo loss of function mutations in the ubiquitin ligase-encoding gene Cullin 3 (CUL3) lead to ASD. In the study described here, we used Cul3 mouse models to evaluate the consequences of Cul3 mutations in vivo. Our results show that Cul3 heterozygous knockout mice exhibit deficits in motor coordination as well as ASD-relevant social and cognitive impairments. Cul3+/-, Cul3+/fl Emx1-Cre and Cul3fl/fl Emx1-Cre mutant brains display cortical lamination abnormalities due to defective migration of post-mitotic excitatory neurons, as well as reduced numbers of excitatory and inhibitory neurons. In line with the observed abnormal cortical organization, Cul3 heterozygous deletion is associated with decreased spontaneous excitatory and inhibitory activity in the cortex. At the molecular level we show that Cul3 regulates cytoskeletal and adhesion protein abundance in the mouse embryonic cortex. Abnormal regulation of cytoskeletal proteins in Cul3 mutant neural cells results in atypical organization of the actin mesh at the cell leading edge. Of note, heterozygous deletion of Cul3 in adult mice does not induce the majority of the behavioral defects observed in constitutive Cul3 haploinsufficient animals, pointing to a critical time-window for Cul3 deficiency. In conclusion, our data indicate that Cul3 plays a critical role in the regulation of cytoskeletal proteins and neuronal migration. ASD-associated defects and behavioral abnormalities are primarily due to dosage sensitive Cul3 functions at early brain developmental stages.

Molecular mechanisms of mitochondrial redox-coupled proton pumping enzymes - Kampjut, Domen
Mitochondria are sites of oxidative phosphorylation in eukaryotic cells. Oxidative phosphorylation operates by a chemiosmotic mechanism made possible by redox-driven proton pumping machines which establish a proton motive force across the inner mitochondrial membrane. This electrochemical proton gradient is used to drive ATP synthesis, which powers the majority of cellular processes such as protein synthesis, locomotion and signalling. In this thesis I investigate the structures and molecular mechanisms of two inner mitochondrial proton pumping enzymes, respiratory complex I and transhydrogenase. I present the first high-resolution structure of the full transhydrogenase from any species, and a significantly improved structure of complex I. Improving the resolution from 3.3 Å available previously to up to 2.3 Å in this thesis allowed us to model bound water molecules, crucial in the proton pumping mechanism. For both enzymes, up to five cryo-EM datasets with different substrates and inhibitors bound were solved to delineate the catalytic cycle and understand the proton pumping mechanism. In transhydrogenase, the proton channel is gated by reversible detachment of the NADP(H)-binding domain which opens the proton channel to the opposite sites of the membrane. In complex I, the proton channels are gated by reversible protonation of key glutamate and lysine residues and breaking of the water wire connecting the proton pumps with the quinone reduction site. The tight coupling between the redox and the proton pumping reactions in transhydrogenase is achieved by controlling the NADP(H) exchange which can only happen when the NADP(H)-binding domain interacts with the membrane domain. In complex I, coupling is achieved by cycling of the whole complex between the closed state, in which quinone can get reduced, and the open state, in which NADH can induce quinol ejection from the binding pocket. On the basis of these results I propose detailed mechanisms for catalytic cycles of transhydrogenase and complex I that are consistent with a large amount of previous work. In both enzymes, conformational and electrostatic mechanisms contribute to the overall catalytic process. Results presented here could be used for better understanding of the human pathologies arising from deficiencies of complex I or transhydrogenase and could be used to develop novel therapies.

Cul3 regulates cytoskeleton protein homeostasis and cell migration during a critical window of brain development - Morandell, Jasmin; Schwarz, Lena A; Basilico, Bernadette; Tasciyan, Saren; Nicolas, Armel; Sommer, Christoph M; Kreuzinger, Caroline; Knaus, Lisa; Dobler, Zoe; Cacci, Emanuele; Danzl, Johann G; Novarino, Gaia (bioRxiv)
De novo loss of function mutations in the ubiquitin ligase-encoding gene Cullin3 (CUL3) lead to autism spectrum disorder (ASD). Here, we used Cul3 mouse models to evaluate the consequences of Cul3 mutations in vivo. Our results show that Cul3 haploinsufficient mice exhibit deficits in motor coordination as well as ASD-relevant social and cognitive impairments. Cul3 mutant brain displays cortical lamination abnormalities due to defective neuronal migration and reduced numbers of excitatory and inhibitory neurons. In line with the observed abnormal columnar organization, Cul3 haploinsufficiency is associated with decreased spontaneous excitatory and inhibitory activity in the cortex. At the molecular level, employing a quantitative proteomic approach, we show that Cul3 regulates cytoskeletal and adhesion protein abundance in mouse embryos. Abnormal regulation of cytoskeletal proteins in Cul3 mutant neuronal cells results in atypical organization of the actin mesh at the cell leading edge, likely causing the observed migration deficits. In contrast to these important functions early in development, Cul3 deficiency appears less relevant at adult stages. In fact, induction of Cul3 haploinsufficiency in adult mice does not result in the behavioral defects observed in constitutive Cul3 haploinsufficient animals. Taken together, our data indicate that Cul3 has a critical role in the regulation of cytoskeletal proteins and neuronal migration and that ASD-associated defects and behavioral abnormalities are primarily due to Cul3 functions at early developmental stages.

Molecular mechanisms for targeted ASD treatments - Basilico, Bernadette; Morandell, Jasmin; Novarino, Gaia (Current Opinion in Genetics and Development)
The possibility to generate construct valid animal models enabled the development and testing of therapeutic strategies targeting the core features of autism spectrum disorders (ASDs). At the same time, these studies highlighted the necessity of identifying sensitive developmental time windows for successful therapeutic interventions. Animal and human studies also uncovered the possibility to stratify the variety of ASDs in molecularly distinct subgroups, potentially facilitating effective treatment design. Here, we focus on the molecular pathways emerging as commonly affected by mutations in diverse ASD-risk genes, on their role during critical windows of brain development and the potential treatments targeting these biological processes.

Lamellipodin tunes cell migration by stabilizing protrusions and promoting adhesion formation - Dimchev, Georgi A; Amiri, Behnam; Humphries, Ashley C.; Schaks, Matthias; Dimchev, Vanessa; Stradal, Theresia E. B.; Faix, Jan; Krause, Matthias; Way, Michael; Falcke, Martin; Rottner, Klemens (Journal of Cell Science)
Efficient migration on adhesive surfaces involves the protrusion of lamellipodial actin networks and their subsequent stabilization by nascent adhesions. The actin-binding protein lamellipodin (Lpd) is thought to play a critical role in lamellipodium protrusion, by delivering Ena/VASP proteins onto the growing plus ends of actin filaments and by interacting with the WAVE regulatory complex, an activator of the Arp2/3 complex, at the leading edge. Using B16-F1 melanoma cell lines, we demonstrate that genetic ablation of Lpd compromises protrusion efficiency and coincident cell migration without altering essential parameters of lamellipodia, including their maximal rate of forward advancement and actin polymerization. We also confirmed lamellipodia and migration phenotypes with CRISPR/Cas9-mediated Lpd knockout Rat2 fibroblasts, excluding cell type-specific effects. Moreover, computer-aided analysis of cell-edge morphodynamics on B16-F1 cell lamellipodia revealed that loss of Lpd correlates with reduced temporal protrusion maintenance as a prerequisite of nascent adhesion formation. We conclude that Lpd optimizes protrusion and nascent adhesion formation by counteracting frequent, chaotic retraction and membrane ruffling.This article has an associated First Person interview with the first author of the paper.
Keywords: Cell Biology

Plants with genetically encoded autoluminescence - Mitiouchkina, Tatiana; Mishin, Alexander S.; Gonzalez Somermeyer, Louisa; Markina, Nadezhda M.; Chepurnyh, Tatiana V.; Guglya, Elena B.; Karataeva, Tatiana A.; Palkina, Kseniia A.; Shakhova, Ekaterina S.; Fakhranurova, Liliia I.; Chekova, Sofia V.; Tsarkova, Aleksandra S.; et al. (Nature Biotechnology)
Autoluminescent plants engineered to express a bacterial bioluminescence gene cluster in plastids have not been widely adopted because of low light output. We engineered tobacco plants with a fungal bioluminescence system that converts caffeic acid (present in all plants) into luciferin and report self-sustained luminescence that is visible to the naked eye. Our findings could underpin development of a suite of imaging tools for plants.

Tension-dependent stabilization of E-cadherin limits cell-cell contact expansion - Slovakova, Jana; Sikora, Mateusz K; Caballero Mancebo, Silvia; Krens, Gabriel; Kaufmann, Walter; Huljev, Karla; Heisenberg, Carl-Philipp J (bioRxiv)
Tension of the actomyosin cell cortex plays a key role in determining cell-cell contact growth and size. The level of cortical tension outside of the cell-cell contact, when pulling at the contact edge, scales with the total size to which a cell-cell contact can grow1,2. Here we show in zebrafish primary germ layer progenitor cells that this monotonic relationship only applies to a narrow range of cortical tension increase, and that above a critical threshold, contact size inversely scales with cortical tension. This switch from cortical tension increasing to decreasing progenitor cell-cell contact size is caused by cortical tension promoting E-cadherin anchoring to the actomyosin cytoskeleton, thereby increasing clustering and stability of E-cadherin at the contact. Once tension-mediated E-cadherin stabilization at the contact exceeds a critical threshold level, the rate by which the contact expands in response to pulling forces from the cortex sharply drops, leading to smaller contacts at physiologically relevant timescales of contact formation. Thus, the activity of cortical tension in expanding cell-cell contact size is limited by tension stabilizing E-cadherin-actin complexes at the contact.

Abstraction based verification of stability of polyhedral switched systems - Garcia Soto, Miriam; Prabhakar, Pavithra (Nonlinear Analysis: Hybrid Systems)
This paper presents a novel abstraction technique for analyzing Lyapunov and asymptotic stability of polyhedral switched systems. A polyhedral switched system is a hybrid system in which the continuous dynamics is specified by polyhedral differential inclusions, the invariants and guards are specified by polyhedral sets and the switching between the modes do not involve reset of variables. A finite state weighted graph abstracting the polyhedral switched system is constructed from a finite partition of the state–space, such that the satisfaction of certain graph conditions, such as the absence of cycles with product of weights on the edges greater than (or equal) to 1, implies the stability of the system. However, the graph is in general conservative and hence, the violation of the graph conditions does not imply instability. If the analysis fails to establish stability due to the conservativeness in the approximation, a counterexample (cycle with product of edge weights greater than or equal to 1) indicating a potential reason for the failure is returned. Further, a more precise approximation of the switched system can be constructed by considering a finer partition of the state–space in the construction of the finite weighted graph. We present experimental results on analyzing stability of switched systems using the above method.

Cellular locomotion using environmental topography - Reversat, Anne; Gärtner, Florian R; Merrin, Jack; Stopp, Julian A; Tasciyan, Saren; Aguilera Servin, Juan L; De Vries, Ingrid; Hauschild, Robert; Hons, Miroslav; Piel, Matthieu; Callan-Jones, Andrew; Voituriez, Raphael; et al. (Nature)
Eukaryotic cells migrate by coupling the intracellular force of the actin cytoskeleton to the environment. While force coupling is usually mediated by transmembrane adhesion receptors, especially those of the integrin family, amoeboid cells such as leukocytes can migrate extremely fast despite very low adhesive forces1. Here we show that leukocytes cannot only migrate under low adhesion but can also transmit forces in the complete absence of transmembrane force coupling. When confined within three-dimensional environments, they use the topographical features of the substrate to propel themselves. Here the retrograde flow of the actin cytoskeleton follows the texture of the substrate, creating retrograde shear forces that are sufficient to drive the cell body forwards. Notably, adhesion-dependent and adhesion-independent migration are not mutually exclusive, but rather are variants of the same principle of coupling retrograde actin flow to the environment and thus can potentially operate interchangeably and simultaneously. As adhesion-free migration is independent of the chemical composition of the environment, it renders cells completely autonomous in their locomotive behaviour.

Metabolic regulation of Drosophila macrophage tissue invasion - Emtenani, Shamsi
Metabolic adaptation is a critical feature of migrating cells. It tunes the metabolic programs of migrating cells to allow them to efficiently exert their crucial roles in development, inflammatory responses and tumor metastasis. Cell migration through physically challenging contexts requires energy. However, how the metabolic reprogramming that underlies in vivo cell invasion is controlled is still unanswered. In my PhD project, I identify a novel conserved metabolic shift in Drosophila melanogaster immune cells that by modulating their bioenergetic potential controls developmentally programmed tissue invasion. We show that this regulation requires a novel conserved nuclear protein, named Atossa. Atossa enhances the transcription of a set of proteins, including an RNA helicase Porthos and two metabolic enzymes, each of which increases the tissue invasion of leading Drosophila macrophages and can rescue the atossa mutant phenotype. Porthos selectively regulates the translational efficiency of a subset of mRNAs containing a 5’-UTR cis-regulatory TOP-like sequence. These 5’TOPL mRNA targets encode mitochondrial-related proteins, including subunits of mitochondrial oxidative phosphorylation (OXPHOS) components III and V and other metabolic-related proteins. Porthos powers up mitochondrial OXPHOS to engender a sufficient ATP supply, which is required for tissue invasion of leading macrophages. Atossa’s two vertebrate orthologs rescue the invasion defect. In my PhD project, I elucidate that Atossa displays a conserved developmental metabolic control to modulate metabolic capacities and the cellular energy state, through altered transcription and translation, to aid the tissue infiltration of leading cells into energy demanding barriers.

Cortical actin properties controlled by Drosophila Fos aid macrophage infiltration against surrounding tissue resistance - Belyaeva, Vera; Wachner, Stephanie; Gridchyn, Igor; Linder, Markus; Emtenani, Shamsi; György, Attila; Sibilia, Maria; Siekhaus, Daria E (bioRxiv)
The infiltration of immune cells into tissues underlies the establishment of tissue resident macrophages, and responses to infections and tumors. Yet the mechanisms immune cells utilize to negotiate tissue barriers in living organisms are not well understood, and a role for cortical actin has not been examined. Here we find that the tissue invasion of Drosophila macrophages, also known as plasmatocytes or hemocytes, utilizes enhanced cortical F-actin levels stimulated by the Drosophila member of the fos proto oncogene transcription factor family (Dfos, Kayak). RNA sequencing analysis and live imaging show that Dfos enhances F-actin levels around the entire macrophage surface by increasing mRNA levels of the membrane spanning molecular scaffold tetraspanin TM4SF, and the actin cross-linking filamin Cheerio which are themselves required for invasion. Cortical F-actin levels are critical as expressing a dominant active form of Diaphanous, a actin polymerizing Formin, can rescue the Dfos Dominant Negative macrophage invasion defect. In vivo imaging shows that Dfos is required to enhance the efficiency of the initial phases of macrophage tissue entry. Genetic evidence argues that this Dfos-induced program in macrophages counteracts the constraint produced by the tension of surrounding tissues and buffers the mechanical properties of the macrophage nucleus from affecting tissue entry. We thus identify tuning the cortical actin cytoskeleton through Dfos as a key process allowing efficient forward movement of an immune cell into surrounding tissues.

Enhancement of proximity induced superconductivity in planar Germanium - Aggarwal, Kushagra; Hofmann, Andrea C; Jirovec, Daniel; Prieto Gonzalez, Ivan; Sammak, Amir; Botifoll, Marc; Marti-Sanchez, Sara; Veldhorst, Menno; Arbiol, Jordi; Scappucci, Giordano; Katsaros, Georgios (arXiv)
Holes in planar Ge have high mobilities, strong spin-orbit interaction and electrically tunable g-factors, and are therefore emerging as a promising candidate for hybrid superconductorsemiconductor devices. This is further motivated by the observation of supercurrent transport in planar Ge Josephson Field effect transistors (JoFETs). A key challenge towards hybrid germanium quantum technology is the design of high quality interfaces and superconducting contacts that are robust against magnetic fields. By combining the assets of Al, which has a long superconducting coherence, and Nb, which has a significant superconducting gap, we form low-disordered JoFETs with large ICRN products that are capable of withstanding high magnetic fields. We furthermore demonstrate the ability of phase-biasing individual JoFETs opening up an avenue to explore topological superconductivity in planar Ge. The persistence of superconductivity in the reported hybrid devices beyond 1.8 T paves the way towards integrating spin qubits and proximity-induced superconductivity on the same chip.

Deep learning-assisted high-throughput analysis of freeze-fracture replica images applied to glutamate receptors and calcium channels at hippocampal synapses - Kleindienst, David; Montanaro-Punzengruber, Jacqueline-Claire; Bhandari, Pradeep; Case, Matthew J; Fukazawa, Yugo; Shigemoto, Ryuichi (International Journal of Molecular Sciences)
The molecular anatomy of synapses defines their characteristics in transmission and plasticity. Precise measurements of the number and distribution of synaptic proteins are important for our understanding of synapse heterogeneity within and between brain regions. Freeze–fracture replica immunogold electron microscopy enables us to analyze them quantitatively on a two-dimensional membrane surface. Here, we introduce Darea software, which utilizes deep learning for analysis of replica images and demonstrate its usefulness for quick measurements of the pre- and postsynaptic areas, density and distribution of gold particles at synapses in a reproducible manner. We used Darea for comparing glutamate receptor and calcium channel distributions between hippocampal CA3-CA1 spine synapses on apical and basal dendrites, which differ in signaling pathways involved in synaptic plasticity. We found that apical synapses express a higher density of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors and a stronger increase of AMPA receptors with synaptic size, while basal synapses show a larger increase in N-methyl-D-aspartate (NMDA) receptors with size. Interestingly, AMPA and NMDA receptors are segregated within postsynaptic sites and negatively correlated in density among both apical and basal synapses. In the presynaptic sites, Cav2.1 voltage-gated calcium channels show similar densities in apical and basal synapses with distributions consistent with an exclusion zone model of calcium channel-release site topography.

Optimal and perfectly parallel algorithms for on-demand data-flow analysis - Chatterjee, Krishnendu; Goharshady, Amir Kafshdar; Ibsen-Jensen, Rasmus; Pavlogiannis, Andreas (European Symposium on Programming)
Interprocedural data-flow analyses form an expressive and useful paradigm of numerous static analysis applications, such as live variables analysis, alias analysis and null pointers analysis. The most widely-used framework for interprocedural data-flow analysis is IFDS, which encompasses distributive data-flow functions over a finite domain. On-demand data-flow analyses restrict the focus of the analysis on specific program locations and data facts. This setting provides a natural split between (i) an offline (or preprocessing) phase, where the program is partially analyzed and analysis summaries are created, and (ii) an online (or query) phase, where analysis queries arrive on demand and the summaries are used to speed up answering queries. In this work, we consider on-demand IFDS analyses where the queries concern program locations of the same procedure (aka same-context queries). We exploit the fact that flow graphs of programs have low treewidth to develop faster algorithms that are space and time optimal for many common data-flow analyses, in both the preprocessing and the query phase. We also use treewidth to develop query solutions that are embarrassingly parallelizable, i.e. the total work for answering each query is split to a number of threads such that each thread performs only a constant amount of work. Finally, we implement a static analyzer based on our algorithms, and perform a series of on-demand analysis experiments on standard benchmarks. Our experimental results show a drastic speed-up of the queries after only a lightweight preprocessing phase, which significantly outperforms existing techniques.

Faster algorithms for quantitative analysis of MCs and MDPs with small treewidth - Asadi, Ali; Chatterjee, Krishnendu; Goharshady, Amir Kafshdar; Mohammadi, Kiarash; Pavlogiannis, Andreas (Automated Technology for Verification and Analysis)
Discrete-time Markov Chains (MCs) and Markov Decision Processes (MDPs) are two standard formalisms in system analysis. Their main associated quantitative objectives are hitting probabilities, discounted sum, and mean payoff. Although there are many techniques for computing these objectives in general MCs/MDPs, they have not been thoroughly studied in terms of parameterized algorithms, particularly when treewidth is used as the parameter. This is in sharp contrast to qualitative objectives for MCs, MDPs and graph games, for which treewidth-based algorithms yield significant complexity improvements. In this work, we show that treewidth can also be used to obtain faster algorithms for the quantitative problems. For an MC with n states and m transitions, we show that each of the classical quantitative objectives can be computed in O((n+m)⋅t2) time, given a tree decomposition of the MC with width t. Our results also imply a bound of O(κ⋅(n+m)⋅t2) for each objective on MDPs, where κ is the number of strategy-iteration refinements required for the given input and objective. Finally, we make an experimental evaluation of our new algorithms on low-treewidth MCs and MDPs obtained from the DaCapo benchmark suite. Our experiments show that on low-treewidth MCs and MDPs, our algorithms outperform existing well-established methods by one or more orders of magnitude.

Polynomial invariant generation for non-deterministic recursive programs - Chatterjee, Krishnendu; Fu, Hongfei; Goharshady, Amir Kafshdar; Goharshady, Ehsan Kafshdar (Proceedings of the 41st ACM SIGPLAN Conference on Programming Language Design and Implementation)
We consider the classical problem of invariant generation for programs with polynomial assignments and focus on synthesizing invariants that are a conjunction of strict polynomial inequalities. We present a sound and semi-complete method based on positivstellensaetze, i.e. theorems in semi-algebraic geometry that characterize positive polynomials over a semi-algebraic set. On the theoretical side, the worst-case complexity of our approach is subexponential, whereas the worst-case complexity of the previous complete method (Kapur, ACA 2004) is doubly-exponential. Even when restricted to linear invariants, the best previous complexity for complete invariant generation is exponential (Colon et al, CAV 2003). On the practical side, we reduce the invariant generation problem to quadratic programming (QCLP), which is a classical optimization problem with many industrial solvers. We demonstrate the applicability of our approach by providing experimental results on several academic benchmarks. To the best of our knowledge, the only previous invariant generation method that provides completeness guarantees for invariants consisting of polynomial inequalities is (Kapur, ACA 2004), which relies on quantifier elimination and cannot even handle toy programs such as our running example.

An efficient algorithm for computing network reliability in small treewidth - Goharshady, Amir Kafshdar; Mohammadi, Fatemeh (Reliability Engineering and System Safety)
We consider the classic problem of Network Reliability. A network is given together with a source vertex, one or more target vertices, and probabilities assigned to each of the edges. Each edge of the network is operable with its associated probability and the problem is to determine the probability of having at least one source-to-target path that is entirely composed of operable edges. This problem is known to be NP-hard. We provide a novel scalable algorithm to solve the Network Reliability problem when the treewidth of the underlying network is small. We also show our algorithm’s applicability for real-world transit networks that have small treewidth, including the metro networks of major cities, such as London and Tokyo. Our algorithm leverages tree decompositions to shrink the original graph into much smaller graphs, for which reliability can be efficiently and exactly computed using a brute force method. To the best of our knowledge, this is the first exact algorithm for Network Reliability that can scale to handle real-world instances of the problem.

Inertial projection-type methods for solving quasi-variational inequalities in real Hilbert spaces - Shehu, Yekini; Gibali, Aviv; Sagratella, Simone (Journal of Optimization Theory and Applications)
In this paper, we introduce an inertial projection-type method with different updating strategies for solving quasi-variational inequalities with strongly monotone and Lipschitz continuous operators in real Hilbert spaces. Under standard assumptions, we establish different strong convergence results for the proposed algorithm. Primary numerical experiments demonstrate the potential applicability of our scheme compared with some related methods in the literature.

Gene amplification as a form of population-level gene expression regulation - Tomanek, Isabella; Grah, Rok; Lagator, M.; Andersson, A. M. C.; Bollback, Jonathan P; Tkačik, Gašper; Guet, Calin C (Nature Ecology & Evolution)
Organisms cope with change by taking advantage of transcriptional regulators. However, when faced with rare environments, the evolution of transcriptional regulators and their promoters may be too slow. Here, we investigate whether the intrinsic instability of gene duplication and amplification provides a generic alternative to canonical gene regulation. Using real-time monitoring of gene-copy-number mutations in Escherichia coli, we show that gene duplications and amplifications enable adaptation to fluctuating environments by rapidly generating copy-number and, therefore, expression-level polymorphisms. This amplification-mediated gene expression tuning (AMGET) occurs on timescales that are similar to canonical gene regulation and can respond to rapid environmental changes. Mathematical modelling shows that amplifications also tune gene expression in stochastic environments in which transcription-factor-based schemes are hard to evolve or maintain. The fleeting nature of gene amplifications gives rise to a generic population-level mechanism that relies on genetic heterogeneity to rapidly tune the expression of any gene, without leaving any genomic signature.

New approaches to reduce friction in turbulent pipe flow - Scarselli, Davide
Many flows encountered in nature and applications are characterized by a chaotic motion known as turbulence. Turbulent flows generate intense friction with pipe walls and are responsible for considerable amounts of energy losses at world scale. The nature of turbulent friction and techniques aimed at reducing it have been subject of extensive research over the last century, but no definite answer has been found yet. In this thesis we show that in pipes at moderate turbulent Reynolds numbers friction is better described by the power law first introduced by Blasius and not by the Prandtl–von Kármán formula. At higher Reynolds numbers, large scale motions gradually become more important in the flow and can be related to the change in scaling of friction. Next, we present a series of new techniques that can relaminarize turbulence by suppressing a key mechanism that regenerates it at walls, the lift–up effect. In addition, we investigate the process of turbulence decay in several experiments and discuss the drag reduction potential. Finally, we examine the behavior of friction under pulsating conditions inspired by the human heart cycle and we show that under such circumstances turbulent friction can be reduced to produce energy savings.

The evolution of gene expression by copy number and point mutations - Tomanek, Isabella
Mutations are the raw material of evolution and come in many different flavors. Point mutations change a single letter in the DNA sequence, while copy number mutations like duplications or deletions add or remove many letters of the DNA sequence simultaneously. Each type of mutation exhibits specific properties like its rate of formation and reversal. Gene expression is a fundamental phenotype that can be altered by both, point and copy number mutations. The following thesis is concerned with the dynamics of gene expression evolution and how it is affected by the properties exhibited by point and copy number mutations. Specifically, we are considering i) copy number mutations during adaptation to fluctuating environments and ii) the interaction of copy number and point mutations during adaptation to constant environments.
Keywords: duplication; amplification; promoter; CNV; AMGET; experimental evolution; Escherichia coli

Salicylic acid targets protein phosphatase 2A to attenuate growth in plants - Tan, Shutang; Abas, Melinda F; Verstraeten, Inge; Glanc, Matous; Molnar, Gergely; Hajny, Jakub; Lasák, Pavel; Petřík, Ivan; Russinova, Eugenia; Petrášek, Jan; Novák, Ondřej; Pospíšil, Jiří; et al. (Current Biology)
Plants, like other multicellular organisms, survive through a delicate balance between growth and defense against pathogens. Salicylic acid (SA) is a major defense signal in plants, and the perception mechanism as well as downstream signaling activating the immune response are known. Here, we identify a parallel SA signaling that mediates growth attenuation. SA directly binds to A subunits of protein phosphatase 2A (PP2A), inhibiting activity of this complex. Among PP2A targets, the PIN2 auxin transporter is hyperphosphorylated in response to SA, leading to changed activity of this important growth regulator. Accordingly, auxin transport and auxin-mediated root development, including growth, gravitropic response, and lateral root organogenesis, are inhibited. This study reveals how SA, besides activating immunity, concomitantly attenuates growth through crosstalk with the auxin distribution network. Further analysis of this dual role of SA and characterization of additional SA-regulated PP2A targets will provide further insights into mechanisms maintaining a balance between growth and defense.

Auxin canalization and vascular tissue formation by TIR1/AFB-mediated auxin signaling in arabidopsis - Mazur, E; Kulik, Ivan; Hajny, Jakub; Friml, Jiří (New Phytologist)
Plant survival depends on vascular tissues, which originate in a self‐organizing manner as strands of cells co‐directionally transporting the plant hormone auxin. The latter phenomenon (also known as auxin canalization) is classically hypothesized to be regulated by auxin itself via the effect of this hormone on the polarity of its own intercellular transport. Correlative observations supported this concept, but molecular insights remain limited. In the current study, we established an experimental system based on the model Arabidopsis thaliana, which exhibits auxin transport channels and formation of vasculature strands in response to local auxin application. Our methodology permits the genetic analysis of auxin canalization under controllable experimental conditions. By utilizing this opportunity, we confirmed the dependence of auxin canalization on a PIN‐dependent auxin transport and nuclear, TIR1/AFB‐mediated auxin signaling. We also show that leaf venation and auxin‐mediated PIN repolarization in the root require TIR1/AFB signaling. Further studies based on this experimental system are likely to yield better understanding of the mechanisms underlying auxin transport polarization in other developmental contexts.

Identification and characterization of the molecular machinery of auxin-dependent canalization during vasculature formation and regeneration - Hajny, Jakub
Self-organization is a hallmark of plant development manifested e.g. by intricate leaf vein patterns, flexible formation of vasculature during organogenesis or its regeneration following wounding. Spontaneously arising channels transporting the phytohormone auxin, created by coordinated polar localizations of PIN-FORMED 1 (PIN1) auxin exporter, provide positional cues for these as well as other plant patterning processes. To find regulators acting downstream of auxin and the TIR1/AFB auxin signaling pathway essential for PIN1 coordinated polarization during auxin canalization, we performed microarray experiments. Besides the known components of general PIN polarity maintenance, such as PID and PIP5K kinases, we identified and characterized a new regulator of auxin canalization, the transcription factor WRKY DNA-BINDING PROTEIN 23 (WRKY23). Next, we designed a subsequent microarray experiment to further uncover other molecular players, downstream of auxin-TIR1/AFB-WRKY23 involved in the regulation of auxin-mediated PIN repolarization. We identified a novel and crucial part of the molecular machinery underlying auxin canalization. The auxin-regulated malectin-type receptor-like kinase CAMEL and the associated leucine-rich repeat receptor-like kinase CANAR target and directly phosphorylate PIN auxin transporters. camel and canar mutants are impaired in PIN1 subcellular trafficking and auxin-mediated repolarization leading to defects in auxin transport, ultimately to leaf venation and vasculature regeneration defects. Our results describe the CAMEL-CANAR receptor complex, which is required for auxin feed-back on its own transport and thus for coordinated tissue polarization during auxin canalization.

Bulk actin dynamics drive phase segregation in zebrafish oocytes - Shamipour, Shayan
Cytoplasm is a gel-like crowded environment composed of tens of thousands of macromolecules, organelles, cytoskeletal networks and cytosol. The structure of the cytoplasm is thought to be highly organized and heterogeneous due to the crowding of its constituents and their effective compartmentalization. In such an environment, the diffusive dynamics of the molecules is very restricted, an effect that is further amplified by clustering and anchoring of molecules. Despite the jammed nature of the cytoplasm at the microscopic scale, large-scale reorganization of cytoplasm is essential for important cellular functions, such as nuclear positioning and cell division. How such mesoscale reorganization of the cytoplasm is achieved, especially for very large cells such as oocytes or syncytial tissues that can span hundreds of micrometers in size, has only begun to be understood. In this thesis, I focus on the recent advances in elucidating the molecular, cellular and biophysical principles underlying cytoplasmic organization across different scales, structures and species. First, I outline which of these principles have been identified by reductionist approaches, such as in vitro reconstitution assays, where boundary conditions and components can be modulated at ease. I then describe how the theoretical and experimental framework established in these reduced systems have been applied to their more complex in vivo counterparts, in particular oocytes and embryonic syncytial structures, and discuss how such complex biological systems can initiate symmetry breaking and establish patterning. Specifically, I examine an example of large-scale reorganizations taking place in zebrafish embryos, where extensive cytoplasmic streaming leads to the segregation of cytoplasm from yolk granules along the animal-vegetal axis of the embryo. Using biophysical experimentation and theory, I investigate the forces underlying this process, to show that this process does not rely on cortical actin reorganization, as previously thought, but instead on a cell-cycle-dependent bulk actin polymerization wave traveling from the animal to the vegetal pole of the embryo. This wave functions in segregation by both pulling cytoplasm animally and pushing yolk granules vegetally. Cytoplasm pulling is mediated by bulk actin network flows exerting friction forces on the cytoplasm, while yolk granule pushing is achieved by a mechanism closely resembling actin comet formation on yolk granules. This study defines a novel role of bulk actin polymerization waves in embryo polarization via cytoplasmic segregation. Lastly, I describe the cytoplasmic reorganizations taking place during zebrafish oocyte maturation, where the initial segregation of the cytoplasm and yolk granules occurs. Here, I demonstrate a previously uncharacterized wave of microtubule aster formation, traveling the oocyte along the animal-vegetal axis. Further research is required to determine the role of such microtubule structures in cytoplasmic reorganizations therein. Collectively, these studies provide further evidence for the coupling between cell cytoskeleton and cell cycle machinery, which can underlie a core self-organizing mechanism for orchestrating large-scale reorganizations in a cell-cycle-tunable manner, where the modulations of the force-generating machinery and cytoplasmic mechanics can be harbored to fulfill cellular functions.

Non-cell-autonomous mechanisms in radial projection neuron migration in the developing cerebral cortex - Hansen, Andi H; Hippenmeyer, Simon (Frontiers in Cell and Developmental Biology)
Concerted radial migration of newly born cortical projection neurons, from their birthplace to their final target lamina, is a key step in the assembly of the cerebral cortex. The cellular and molecular mechanisms regulating the specific sequential steps of radial neuronal migration in vivo are however still unclear, let alone the effects and interactions with the extracellular environment. In any in vivo context, cells will always be exposed to a complex extracellular environment consisting of (1) secreted factors acting as potential signaling cues, (2) the extracellular matrix, and (3) other cells providing cell–cell interaction through receptors and/or direct physical stimuli. Most studies so far have described and focused mainly on intrinsic cell-autonomous gene functions in neuronal migration but there is accumulating evidence that non-cell-autonomous-, local-, systemic-, and/or whole tissue-wide effects substantially contribute to the regulation of radial neuronal migration. These non-cell-autonomous effects may differentially affect cortical neuron migration in distinct cellular environments. However, the cellular and molecular natures of such non-cell-autonomous mechanisms are mostly unknown. Furthermore, physical forces due to collective migration and/or community effects (i.e., interactions with surrounding cells) may play important roles in neocortical projection neuron migration. In this concise review, we first outline distinct models of non-cell-autonomous interactions of cortical projection neurons along their radial migration trajectory during development. We then summarize experimental assays and platforms that can be utilized to visualize and potentially probe non-cell-autonomous mechanisms. Lastly, we define key questions to address in the future.

Lineage tracing and clonal analysis in developing cerebral cortex using mosaic analysis with double markers (MADM) - Beattie, Robert J; Streicher, Carmen; Amberg, Nicole; Cheung, Giselle T; Contreras, Ximena; Hansen, Andi H; Hippenmeyer, Simon (Journal of Visual Experiments)
Beginning from a limited pool of progenitors, the mammalian cerebral cortex forms highly organized functional neural circuits. However, the underlying cellular and molecular mechanisms regulating lineage transitions of neural stem cells (NSCs) and eventual production of neurons and glia in the developing neuroepithelium remains unclear. Methods to trace NSC division patterns and map the lineage of clonally related cells have advanced dramatically. However, many contemporary lineage tracing techniques suffer from the lack of cellular resolution of progeny cell fate, which is essential for deciphering progenitor cell division patterns. Presented is a protocol using mosaic analysis with double markers (MADM) to perform in vivo clonal analysis. MADM concomitantly manipulates individual progenitor cells and visualizes precise division patterns and lineage progression at unprecedented single cell resolution. MADM-based interchromosomal recombination events during the G2-X phase of mitosis, together with temporally inducible CreERT2, provide exact information on the birth dates of clones and their division patterns. Thus, MADM lineage tracing provides unprecedented qualitative and quantitative optical readouts of the proliferation mode of stem cell progenitors at the single cell level. MADM also allows for examination of the mechanisms and functional requirements of candidate genes in NSC lineage progression. This method is unique in that comparative analysis of control and mutant subclones can be performed in the same tissue environment in vivo. Here, the protocol is described in detail, and experimental paradigms to employ MADM for clonal analysis and lineage tracing in the developing cerebral cortex are demonstrated. Importantly, this protocol can be adapted to perform MADM clonal analysis in any murine stem cell niche, as long as the CreERT2 driver is present.

Genetic dissection of neural development in health and disease at single cell resolution - Contreras, Ximena
Mosaic genetic analysis has been widely used in different model organisms such as the fruit fly to study gene-function in a cell-autonomous or tissue-specific fashion. More recently, and less easily conducted, mosaic genetic analysis in mice has also been enabled with the ambition to shed light on human gene function and disease. These genetic tools are of particular interest, but not restricted to, the study of the brain. Notably, the MADM technology offers a genetic approach in mice to visualize and concomitantly manipulate small subsets of genetically defined cells at a clonal level and single cell resolution. MADM-based analysis has already advanced the study of genetic mechanisms regulating brain development and is expected that further MADM-based analysis of genetic alterations will continue to reveal important insights on the fundamental principles of development and disease to potentially assist in the development of new therapies or treatments. In summary, this work completed and characterized the necessary genome-wide genetic tools to perform MADM-based analysis at single cell level of the vast majority of mouse genes in virtually any cell type and provided a protocol to perform lineage tracing using the novel MADM resource. Importantly, this work also explored and revealed novel aspects of biologically relevant events in an in vivo context, such as the chromosome-specific bias of chromatid sister segregation pattern, the generation of cell-type diversity in the cerebral cortex and in the cerebellum and finally, the relevance of the interplay between the cell-autonomous gene function and cell-non-autonomous (community) effects in radial glial progenitor lineage progression. This work provides a foundation and opens the door to further elucidating the molecular mechanisms underlying neuronal diversity and astrocyte generation.

Zena Werb (1945-2020): Cell biology in context - Sixt, Michael K; Huttenlocher, Anna (The Journal of Cell Biology)

Functional innovations of PIN auxin transporters mark crucial evolutionary transitions during rise of flowering plants - Zhang, Yuzhou; Rodriguez Solovey, Lesia; Li, Lanxin; Zhang, Xixi; Friml, Jiří (Science Advances)
Flowering plants display the highest diversity among plant species and have notably shaped terrestrial landscapes. Nonetheless, the evolutionary origin of their unprecedented morphological complexity remains largely an enigma. Here, we show that the coevolution of cis-regulatory and coding regions of PIN-FORMED (PIN) auxin transporters confined their expression to certain cell types and directed their subcellular localization to particular cell sides, which together enabled dynamic auxin gradients across tissues critical to the complex architecture of flowering plants. Extensive intraspecies and interspecies genetic complementation experiments with PINs from green alga up to flowering plant lineages showed that PIN genes underwent three subsequent, critical evolutionary innovations and thus acquired a triple function to regulate the development of three essential components of the flowering plant Arabidopsis: shoot/root, inflorescence, and floral organ. Our work highlights the critical role of functional innovations within the PIN gene family as essential prerequisites for the origin of flowering plants.

AcoMYB4, an Ananas comosus L. MYB transcription factor, functions in osmotic stress through negative regulation of ABA signaling - Chen, Huihuang; Lai, Linyi; Li, Lanxin; Liu, Liping; Jakada, Bello Hassan; Huang, Youmei; He, Qing; Chai, Mengnan; Niu, Xiaoping; Qin, Yuan (International Journal of Molecular Sciences)
Drought and salt stress are the main environmental cues affecting the survival, development, distribution, and yield of crops worldwide. MYB transcription factors play a crucial role in plants’ biological processes, but the function of pineapple MYB genes is still obscure. In this study, one of the pineapple MYB transcription factors, AcoMYB4, was isolated and characterized. The results showed that AcoMYB4 is localized in the cell nucleus, and its expression is induced by low temperature, drought, salt stress, and hormonal stimulation, especially by abscisic acid (ABA). Overexpression of AcoMYB4 in rice and Arabidopsis enhanced plant sensitivity to osmotic stress; it led to an increase in the number stomata on leaf surfaces and lower germination rate under salt and drought stress. Furthermore, in AcoMYB4 OE lines, the membrane oxidation index, free proline, and soluble sugar contents were decreased. In contrast, electrolyte leakage and malondialdehyde (MDA) content increased significantly due to membrane injury, indicating higher sensitivity to drought and salinity stresses. Besides the above, both the expression level and activities of several antioxidant enzymes were decreased, indicating lower antioxidant activity in AcoMYB4 transgenic plants. Moreover, under osmotic stress, overexpression of AcoMYB4 inhibited ABA biosynthesis through a decrease in the transcription of genes responsible for ABA synthesis (ABA1 and ABA2) and ABA signal transduction factor ABI5. These results suggest that AcoMYB4 negatively regulates osmotic stress by attenuating cellular ABA biosynthesis and signal transduction pathways.

Experimental toolbox for quantitative evaluation of clathrin-mediated endocytosis in the plant model Arabidopsis - Johnson, Alexander J; Gnyliukh, Nataliia; Kaufmann, Walter; Narasimhan, Madhumitha; Vert, G; Bednarek, SY; Friml, Jiří (Journal of Cell Science)
Clathrin-mediated endocytosis (CME) is a crucial cellular process implicated in many aspects of plant growth, development, intra- and inter-cellular signaling, nutrient uptake and pathogen defense. Despite these significant roles, little is known about the precise molecular details of how it functions in planta. In order to facilitate the direct quantitative study of plant CME, here we review current routinely used methods and present refined, standardized quantitative imaging protocols which allow the detailed characterization of CME at multiple scales in plant tissues. These include: (i) an efficient electron microscopy protocol for the imaging of Arabidopsis CME vesicles in situ, thus providing a method for the detailed characterization of the ultra-structure of clathrin-coated vesicles; (ii) a detailed protocol and analysis for quantitative live-cell fluorescence microscopy to precisely examine the temporal interplay of endocytosis components during single CME events; (iii) a semi-automated analysis to allow the quantitative characterization of global internalization of cargos in whole plant tissues; and (iv) an overview and validation of useful genetic and pharmacological tools to interrogate the molecular mechanisms and function of CME in intact plant samples.

All roads lead to auxin: Post-translational regulation of auxin transport by multiple hormonal pathways - Semeradova, Hana; Montesinos López, Juan C; Benková, Eva (Plant Communications)
Auxin is a key hormonal regulator, that governs plant growth and development in concert with other hormonal pathways. The unique feature of auxin is its polar, cell-to-cell transport that leads to the formation of local auxin maxima and gradients, which coordinate initiation and patterning of plant organs. The molecular machinery mediating polar auxin transport is one of the important points of interaction with other hormones. Multiple hormonal pathways converge at the regulation of auxin transport and form a regulatory network that integrates various developmental and environmental inputs to steer plant development. In this review, we discuss recent advances in understanding the mechanisms that underlie regulation of polar auxin transport by multiple hormonal pathways. Specifically, we focus on the post-translational mechanisms that contribute to fine-tuning of the abundance and polarity of auxin transporters at the plasma membrane and thereby enable rapid modification of the auxin flow to coordinate plant growth and development.

ARCH-COMP19 Category Report: Hybrid systems with piecewise constant dynamics - Frehse, Goran; Abate, Alessandro; Adzkiya, Dieky; Becchi, Anna; Bu, Lei; Cimatti, Alessandro; Giacobbe, Mirco; Griggio, Alberto; Mover, Sergio; Mufid, Muhammad Syifa'ul; Riouak, Idriss; Tonetta, Stefano; et al. (ARCH19. 6th International Workshop on Applied Verification of Continuous and Hybrid Systems)
This report presents the results of a friendly competition for formal verification of continuous and hybrid systems with piecewise constant dynamics. The friendly competition took place as part of the workshop Applied Verification for Continuous and Hybrid Systems (ARCH) in 2019. In this third edition, six tools have been applied to solve five different benchmark problems in the category for piecewise constant dynamics: BACH, Lyse, Hy- COMP, PHAVer/SX, PHAVerLite, and VeriSiMPL. Compared to last year, a new tool has participated (HyCOMP) and PHAVerLite has replaced PHAVer-lite. The result is a snap- shot of the current landscape of tools and the types of benchmarks they are particularly suited for. Due to the diversity of problems, we are not ranking tools, yet the presented results probably provide the most complete assessment of tools for the safety verification of continuous and hybrid systems with piecewise constant dynamics up to this date.

Tropical formulae for summation over a part of SL(2,Z) - Kalinin, Nikita; Shkolnikov, Mikhail (European Journal of Mathematics)

Studying YAP-mediated 3D morphogenesis using fish embryos and human spheroids - Asaoka, Yoichi; Morita, Hitoshi; Furumoto, Hiroko; Heisenberg, Carl-Philipp J; Furutani-Seiki, Makoto (The hippo pathway)
The transcription coactivator, Yes-associated protein (YAP), which is a nuclear effector of the Hippo signaling pathway, has been shown to be a mechano-transducer. By using mutant fish and human 3D spheroids, we have recently demonstrated that YAP is also a mechano-effector. YAP functions in three-dimensional (3D) morphogenesis of organ and global body shape by controlling actomyosin-mediated tissue tension. In this chapter, we present a platform that links the findings in fish embryos with human cells. The protocols for analyzing tissue tension-mediated global body shape/organ morphogenesis in vivo and ex vivo using medaka fish embryos and in vitro using human cell spheroids represent useful tools for unraveling the molecular mechanisms by which YAP functions in regulating global body/organ morphogenesis.

Per-session security: Password-based cryptography revisited - Demay, Gregory; Gazi, Peter; Maurer, Ueli; Tackmann, Bjorn (Journal of Computer Security)
Cryptographic security is usually defined as a guarantee that holds except when a bad event with negligible probability occurs, and nothing is guaranteed in that bad case. However, in settings where such failure can happen with substantial probability, one needs to provide guarantees even for the bad case. A typical example is where a (possibly weak) password is used instead of a secure cryptographic key to protect a session, the bad event being that the adversary correctly guesses the password. In a situation with multiple such sessions, a per-session guarantee is desired: any session for which the password has not been guessed remains secure, independently of whether other sessions have been compromised. A new formalism for stating such gracefully degrading security guarantees is introduced and applied to analyze the examples of password-based message authentication and password-based encryption. While a natural per-message guarantee is achieved for authentication, the situation of password-based encryption is more delicate: a per-session confidentiality guarantee only holds against attackers for which the distribution of password-guessing effort over the sessions is known in advance. In contrast, for more general attackers without such a restriction, a strong, composable notion of security cannot be achieved.

Simplices modelled on spaces of constant curvature - Dyer, Ramsay; Vegter, Gert; Wintraecken, Mathijs (Journal of Computational Geometry)
We give non-degeneracy criteria for Riemannian simplices based on simplices in spaces of constant sectional curvature. It extends previous work on Riemannian simplices, where we developed Riemannian simplices with respect to Euclidean reference simplices. The criteria we give in this article are in terms of quality measures for spaces of constant curvature that we develop here. We see that simplices in spaces that have nearly constant curvature, are already non-degenerate under very weak quality demands. This is of importance because it allows for sampling of Riemannian manifolds based on anisotropy of the manifold and not (absolute) curvature.

Simple verifiable delay functions - Pietrzak, Krzysztof Z (10th Innovations in Theoretical Computer Science Conference)
We construct a verifiable delay function (VDF) by showing how the Rivest-Shamir-Wagner time-lock puzzle can be made publicly verifiable. Concretely, we give a statistically sound public-coin protocol to prove that a tuple (N,x,T,y) satisfies y=x2T (mod N) where the prover doesn’t know the factorization of N and its running time is dominated by solving the puzzle, that is, compute x2T, which is conjectured to require T sequential squarings. To get a VDF we make this protocol non-interactive using the Fiat-Shamir heuristic.The motivation for this work comes from the Chia blockchain design, which uses a VDF as akey ingredient. For typical parameters (T≤2 40, N= 2048), our proofs are of size around 10K B, verification cost around three RSA exponentiations and computing the proof is 8000 times faster than solving the puzzle even without any parallelism.

Formal synthesis of stabilizing controllers for periodically controlled linear switched systems - Kundu, Atreyee; Garcia Soto, Miriam; Prabhakar, Pavithra (5th Indian Control Conference Proceedings)
In this paper, we address the problem of synthesizing periodic switching controllers for stabilizing a family of linear systems. Our broad approach consists of constructing a finite game graph based on the family of linear systems such that every winning strategy on the game graph corresponds to a stabilizing switching controller for the family of linear systems. The construction of a (finite) game graph, the synthesis of a winning strategy and the extraction of a stabilizing controller are all computationally feasible. We illustrate our method on an example.

The extrinsic nature of the Hausdorff distance of optimal triangulations of manifolds - Vegter, Gert; Wintraecken, Mathijs (The 31st Canadian Conference in Computational Geometry)
Fejes Tóth [5] and Schneider [9] studied approximations of smooth convex hypersurfaces in Euclidean space by piecewise flat triangular meshes with a given number of vertices on the hypersurface that are optimal with respect to Hausdorff distance. They proved that this Hausdorff distance decreases inversely proportional with m 2/(d−1), where m is the number of vertices and d is the dimension of Euclidean space. Moreover the pro-portionality constant can be expressed in terms of the Gaussian curvature, an intrinsic quantity. In this short note, we prove the extrinsic nature of this constant for manifolds of sufficiently high codimension. We do so by constructing an family of isometric embeddings of the flat torus in Euclidean space.

Topological data analysis in information space - Edelsbrunner, Herbert; Virk, Ziga; Wagner, Hubert (35th International Symposium on Computational Geometry)
Various kinds of data are routinely represented as discrete probability distributions. Examples include text documents summarized by histograms of word occurrences and images represented as histograms of oriented gradients. Viewing a discrete probability distribution as a point in the standard simplex of the appropriate dimension, we can understand collections of such objects in geometric and topological terms. Importantly, instead of using the standard Euclidean distance, we look into dissimilarity measures with information-theoretic justification, and we develop the theory needed for applying topological data analysis in this setting. In doing so, we emphasize constructions that enable the usage of existing computational topology software in this context.

Optimized reaction pair of the CysHis tag and Ni(II)-NTA probe for highly selective chemical labeling of membrane proteins - Zenmyo, Naoki; Tokumaru, Hiroki; Uchinomiya, Shohei; Fuchida, Hirokazu; Tabata, Shigekazu; Hamachi, Itaru; Shigemoto, Ryuichi; Ojida, Akio (Bulletin of the Chemical Society of Japan)
Chemical labeling of proteins with synthetic molecular probes offers the possibility to probe the functions of proteins of interest in living cells. However, the methods for covalently labeling targeted proteins using complementary peptide tag-probe pairs are still limited, irrespective of the versatility of such pairs in biological research. Herein, we report the new CysHis tag-Ni(II) probe pair for the specific covalent labeling of proteins. A broad-range evaluation of the reactivity profiles of the probe and the CysHis peptide tag afforded a tag-probe pair with an optimized and high labeling selectivity and reactivity. In particular, the labeling specificity of this pair was notably improved compared to the previously reported one. This pair was successfully utilized for the fluorescence imaging of membrane proteins on the surfaces of living cells, demonstrating its potential utility in biological research.

Testing the complexity of a valued CSP language - Kolmogorov, Vladimir (46th International Colloquium on Automata, Languages and Programming)
A Valued Constraint Satisfaction Problem (VCSP) provides a common framework that can express a wide range of discrete optimization problems. A VCSP instance is given by a finite set of variables, a finite domain of labels, and an objective function to be minimized. This function is represented as a sum of terms where each term depends on a subset of the variables. To obtain different classes of optimization problems, one can restrict all terms to come from a fixed set Γ of cost functions, called a language. Recent breakthrough results have established a complete complexity classification of such classes with respect to language Γ: if all cost functions in Γ satisfy a certain algebraic condition then all Γ-instances can be solved in polynomial time, otherwise the problem is NP-hard. Unfortunately, testing this condition for a given language Γ is known to be NP-hard. We thus study exponential algorithms for this meta-problem. We show that the tractability condition of a finite-valued language Γ can be tested in O(3‾√3|D|⋅poly(size(Γ))) time, where D is the domain of Γ and poly(⋅) is some fixed polynomial. We also obtain a matching lower bound under the Strong Exponential Time Hypothesis (SETH). More precisely, we prove that for any constant δ<1 there is no O(3‾√3δ|D|) algorithm, assuming that SETH holds.

Sampling the integers with low relative error - Walter, Michael (Progress in Cryptology – AFRICACRYPT 2019)
Randomness is an essential part of any secure cryptosystem, but many constructions rely on distributions that are not uniform. This is particularly true for lattice based cryptosystems, which more often than not make use of discrete Gaussian distributions over the integers. For practical purposes it is crucial to evaluate the impact that approximation errors have on the security of a scheme to provide the best possible trade-off between security and performance. Recent years have seen surprising results allowing to use relatively low precision while maintaining high levels of security. A key insight in these results is that sampling a distribution with low relative error can provide very strong security guarantees. Since floating point numbers provide guarantees on the relative approximation error, they seem a suitable tool in this setting, but it is not obvious which sampling algorithms can actually profit from them. While previous works have shown that inversion sampling can be adapted to provide a low relative error (Pöppelmann et al., CHES 2014; Prest, ASIACRYPT 2017), other works have called into question if this is possible for other sampling techniques (Zheng et al., Eprint report 2018/309). In this work, we consider all sampling algorithms that are popular in the cryptographic setting and analyze the relationship of floating point precision and the resulting relative error. We show that all of the algorithms either natively achieve a low relative error or can be adapted to do so.